Temporal variation in environmental DNA detections within an urban estuary - Joseph D. DiBattista; Ashley M. Fowler; David Harasti; Robert Hitchen; Nicole McMahon; Shaun P. Wilkinson (Regional Studies in Marine Science, 2026)

Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

Scaling of Short‐Duration, Summer Rainfall Event Temporal Profiles With Warming Over Great Britain - Alexandra Seawell; Hayley J. Fowler; Stephen Blenkinsop; Caspar J. M. Hewett; Roberto Villalobos Herrera; Marie Hundhausen; Haider Ali (International Journal of Climatology, 2026)
The relationship between extreme rainfall and temperature, known as temperature scaling, is widely used to understand changes in rainfall characteristics under a warming climate. While most previous studies have focussed on fixed‐duration intensities or event totals, this study examines how different aspects of the rainfall temporal profile respond to temperature. Specifically, we focus on temperature scaling of total event depth, maximum sub‐hourly intensity and measures of profile concentration and loading. Using both sub‐hourly rain gauge data across Britain and 10‐min output from a convection‐permitting climate model (CPM) for present and future climates over southern England and Wales, we analyse short‐duration, summer rainstorms. Results show that total rainfall depth increases with temperature, with higher quantiles approaching Clausius‐Clapeyron (CC) scaling rates of 6–7%°C −1 . However, changes are unevenly distributed within the rainfall event temporal structure. Maximum sub‐hourly intensities scale more strongly than total event depth, with upper quantiles reaching 7–11%°C −1 , indicating pronounced intensification of short‐duration rainfall extremes at high temperatures. Accumulation of 50% of the rainfall event volume was found to occur over a shorter fraction of the storm duration and earlier in the storm duration, indicating rainfall events are more concentrated and more front‐loaded at higher temperatures, with both scaling at rates of 1–2%°C −1 . These results suggest that future summer rainstorms will not only deliver greater overall rainfall in a warming climate, but also produce more intense and earlier bursts of precipitation, heightening flash flood risk. Disregarding these temporal shifts may lead to underestimation of flood hazards and misrepresentation of climate change impacts in hydrological modelling and infrastructure design.

A conservation behaviour approach to the mitigation hierarchy for anthropogenic stressors - Kathleen D.W. Church; Brett M. Seymoure; Shannon Crossen; Kasey D. Fowler-Finn; Matthew K. LeFauve; Jennifer N. Phillips; Bruce A. Schulte (Animal Behaviour, 2026)

Correlating eDNA indices of relative biomass and abundance with those derived from electrofishing for two ecologically disparate Australian freshwater species - Meaghan L. Rourke; Matt K. Broadhurst; Ashley M. Fowler; Julian M. Hughes; Jason D. Thiem; Golam Sarwer; D. Stewart Fielder; Elise M. Furlan (Aquatic Sciences, 2026)
In response to increasing global interest in the utility of environmental DNA (eDNA) for non-invasively monitoring fish populations, the relationships between eDNA concentrations and electrofishing-derived relative biomasses and abundances were assessed for two ecologically distinct Australian native freshwater species: Murray cod ( Maccullochella peelii ) and bony herring ( Nematalosa erebi ). Species-specific eDNA assays targeting mitochondrial 12S rRNA were applied using quantitative PCR (qPCR) to filtered water samples collected concurrently with boat electrofishing at five sites in each of three rivers in New South Wales during autumn, 2021 and 2022. While eDNA concentrations were low, we identified significant positive correlations with relative biomass and abundance for both species, albeit strongest for bony herring, which unlike the mostly solitary Murray cod, occur in dense schools. Regardless of species, daily river discharge was negatively correlated with eDNA concentrations, possibly owing to dilution effects. The results support the feasibility of using eDNA to monitor fish populations in dynamic riverine systems, although future work is required to refine sampling protocols and better investigate the effects of various biotic and abiotic factors that might influence relationships.

Insights from three decades of IUCN Red List assessments catalyzing shark, ray, and chimaera conservation - Brittany Finucci; Cassandra L. Rigby; Nicholas K. Dulvy; Rachel D. Cavanagh; Sarah Fowler; Lucy R. Harrison; Julia M. Lawson; Riley Pollom; Colin A. Simpfendorfer; Rachel H. L. Walls; Rima W. Jabado (Conservation Biology, 2026)
The International Union for Conservation of Nature (IUCN) Red List of Threatened Species is a critical measure of global aquatic and terrestrial biodiversity status. It is also the basis for the Red List Index, which tracks extinction risk over time. Sharks, rays, and chimaeras (Chondrichthyes) have now been comprehensively assessed twice (1996–2011 and 2012–2021) with hindcast assessments from 1970 onward, yielding an unprecedented extinction risk trajectory for an aquatic vertebrate class. The three‐decade success of the IUCN Species Survival Commission (SSC) Shark Specialist Group (SSG) in providing updated and evidence‐based assessments stems from sustained and coordinated activities by SSG members. We examined how a community of dedicated experts organized to fill gaps in key information to inform Red List assessments. From this evaluation, we identified six key lessons related to membership, taxonomic changes, implementation of the precautionary approach, information prioritization, assessment standardization, and policy efforts. However, existing challenges, including resource constraints and assessment discrepancies at different spatial scales, need to be addressed to ensure Red List assessments stay on pace with advances in conservation. With the second global assessment of chondrichthyans completed, it is appropriate to reflect on the evolution of the SSG and its achievements over three decades to highlight new tools and approaches to red listing and to identify priorities for the immediate future that are also applicable to other aquatic taxa with limited data, slow life histories, and exposure to high levels of fishing.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Global manta and devil ray population declines: Closing policy and management gaps to reduce fisheries mortality - Betty J.L. Laglbauer; Nidhi G. D'Costa; Joshua D. Stewart; Marta D. Palacios; Melissa Cronin; Daniel Fernando; Nerea Lezama-Ochoa; Asia O. Armstrong; Rima W. Jabado; Sarah Fowler; Julia M. Lawson; Olga Koubrak; et al. (Biological Conservation, 2026)

Responsible restocking to aid recovery of an iconic sciaenid fishery: A case study of Mulloway (Argyrosomus japonicus) - Alistair Becker; Julian M. Hughes; Ashley M. Fowler; Matthew D. Taylor (Fisheries Research, 2026)

Raman spectroscopy is a non-invasive method to predict the total viable microbial count through the packaging material of vacuum packaged lamb meat - Benjamin W.B. Holman; David L. Hopkins; Stephanie M. Fowler (Meat Science, 2025)

Linking Climate and Demography to Predict Population Dynamics and Persistence Under Global Change - Jennifer L. Williams; Amy L. Angert; Aldo Compagnoni; Ali Campbell; Megan L. DeMarche; Margaret E. K. Evans; Joshua C. Fowler; Edgar J. González; Amy M. Iler; Jenna A. Loesberg; Allison M. Louthan; Alexandra B. Martin; et al. (Ecology Letters, 2025)
Predicting the effects of climate change on plant and animal populations is an urgent challenge for understanding the fate of biodiversity under global change. At the surface, quantifying how climate drives the vital rates that underlie population dynamics appears simple, yet many decisions are required to connect climate to demographic data. Competing approaches have emerged in the literature with little consensus around best practices. Here we provide a practical guide for how to best link vital rates to climate for the purposes of inference and projection of population dynamics. We first describe the sources of demographic and climate data underlying population models. We then focus on best practices to model the relationships between vital rates and climate, highlighting what we can learn from mechanistic and phenomenological models. Finally, we discuss the challenges of prediction and forecasting in the face of uncertainty about climate‐demographic relationships as well as future climate. We conclude by suggesting ways forward to build this field of research into one that makes robust forecasts of population persistence, with opportunities for synthesis across species.

Caribbean Creep meets Chesapeake Creep: marine bioinvasions and community shifts along the Mid-Atlantic Coast, USA - Amy E. Fowler; April M. H. Blakeslee; Andrew Davinack; Robert Aguilar; Miranda Andersen; Clara Benadon; Henry H. C. Choong; Lindsay Green-Gavrielidis; Sarah R. Greenberg; El Hartshorn; Niels-Viggo Hobbs; Sara Labbe; et al. (Biological Invasions, 2025)
The Mid-Atlantic waters of North America are warming faster than > 90% of other global oceans, leading to significant increases in bottom water temperatures and influencing shifts in marine community structure. Given this modern-day scenario of significant community shifts over space and time, baseline surveys of species diversity are increasingly valuable. Therefore, we performed the first-ever marine bioinvasions Rapid Assessment Survey (RAS) along the Mid-Atlantic waters of the United States in June 2023, focused on marina floating pontoons in Virginia, Maryland, Delaware, and New Jersey. We recorded 29 non-indigenous, 16 cryptogenic, and 10 species that have expanded their ranges in the mid-Atlantic. Seven of these 10 species have expanded northwards from southern locations in the Caribbean (“Caribbean Creep”) or the western Atlantic (“Chesapeake Creep”), and three have expanded southwards. Five non-indigenous species (NIS) were found at more than 60% of the 10 sampled sites: the bryozoans Bugula neritina , Schizoporella pungens , Tricellaria inopinata, macroalgae Codium fragile subsp. fragile , and the sea anemone Aiptasiogeton eruptaurantia . We did not document any new nonindigenous species not already recorded on the Western Atlantic coast. All 10 communities were distinctly different, and species dominance varied by latitude and by site. This first-ever RAS of the Mid-Atlantic waters of the United States provides critical insight into how marine communities have been and are changing as a result of colonization by NIS, including those that have expanded their ranges as a result of human-induced climate change.

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Patterns and drivers of movement in the estuary-associated sparid Acanthopagrus australis from a large-scale tagging study - Holly Gunton; Ashley M. Fowler; David J. Booth; John Stewart (Fisheries Research, 2025)

Combined Ca, Sr isotope and trace element analyses of Late Cretaceous dinosaur teeth: assessing diet versus diagenesis - Mateusz M. Michailow; Federico Lugli; Anna Cipriani; Francesco Della Giustina; Annalisa Ferretti; Daniele Malferrari; Denver Fowler; Elizabeth Freedman Fowler; Michael Weber; Thomas Tütken (Geochimica et Cosmochimica Acta, 2025)

Remote sensing, petrogenesis and tectono-magmatic evolution of the Wadi Queh-Wadi Abu Shigeili area: a window into the transitional history of the central Egyptian-Nubian Shield from pre-plate collision to post-collision magmatism - Osama K. Dessouky; El-Sayed H. El-Sawey; Yasser S. Badr; Sobhi Nasir; Gehad M. Saleh; Ahmed M. Dardier; Kamal A. Ali; Abdel-Rahman Fowler; Saleh E. Ammar; Ahmed M. Ismail; Mahmoud M. Hassan (International Journal of Earth Sciences, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Variable post-capture condition estimated by visual assessment for key recreational species discarded in a nearshore marine charter fishery off eastern Australia - Julian M. Hughes; Daniel D. Johnson; Faith A. Ochwada-Doyle; Jeffrey J. Murphy; Matthew D. Taylor; Ashley M. Fowler (Fisheries Research, 2025)

Chewing requirements and glycemic response of fibrous feedstuffs - A.L. Fowler; C. Guinard; N.A. Imbeault; V.L. Erwin; I.N. Grayston; P. Sweetman; M. Winchester; J.D. Pagan (Journal of Equine Veterinary Science, 2025)

Differential survival of Ilyanassa obsoleta to water temperature and association with the non-native red alga Gracilaria vermiculophylla - Timothy S. Lee; Amy E. Fowler; Jessica R. Largen; Jonathan P. Russo; Zackary J. Schlegel; Dawson K. Wright; April M. H. Blakeslee (Hydrobiologia, 2025)
Along the U.S. east coast, the widespread non-native red alga Gracilaria vermiculophylla provides habitat for an array of macroinvertebrates, including the eastern mudsnail Ilyanassa obsoleta . Though I. obsoleta tolerates a wide temperature range, increases in summer water temperatures may enhance mortality; furthermore, the presence of non-native algae in rising seawater temperatures could exacerbate harmful conditions. We tested how the presence or absence of G. vermiculophylla influenced snail mortality across a range of summer temperatures over a 3-week period. We found that I. obsoleta survived the longest in the lowest temperature (27 °C), followed by the medium (32 °C), and lastly the highest (36 °C) where all snails died within 2 days. Mortality was also higher and faster for snails in the presence versus absence of G. vermiculophylla . We suspected dissolved oxygen became very low at the higher temperatures with G. vermiculophylla ; thus we conducted a laboratory-based dissolved oxygen experiment. We found that G. vermiculophylla degraded and oxygen declined faster at the highest temperature treatment, thereby creating anoxic conditions. Altogether, our results demonstrate that G. vermiculophylla could enhance anoxic conditions at high summer temperatures, potentially leading to enhanced faunal mortality.

Identifying capacity limitations and training needs using a stock assessment game - André E. Punt; Catherine M. Dichmont; Natalie A. Dowling; Roy A. Deng; Sean Pascoe; Ingrid van Putten; Pia Bessell-Browne; Paul Burch; Owen Burnell; Rowan C. Chick; Simon de Lestang; Ainslie Denham; et al. (Fisheries Research, 2025)

Early life history traits and elevated growth trajectories associated with survival into winter in range-expanding coral reef fish - Alexander L. Rigg; Ashley M. Fowler; Brigitte Sommer; David J. Booth (Marine Biology, 2025)
Climate change is driving the poleward range expansion of sub-tropical and tropical marine species into temperate ecosystems, with ocean-warming hotspots experiencing rapid shifts in species distributions. While recruitment to temperate waters by expatriating tropical vagrant fish is increasing, surviving through the cooler winters remains a significant barrier to their establishment. This study investigates the links between early life history traits and survival into winter in the Sergeant Major ( Abudefduf vaigiensis ), a tropical damselfish expanding its range into temperate southeastern Australia. Using otolith microstructure analysis, we reconstructed the early life histories of 122 individuals collected from rocky reefs in Sydney (33.8 o S) Australia in 2022 and 2023 and assessed their early life history traits. Our results demonstrate that individuals sampled during winter (hereafter “wintered fish”) had a larger size at hatching, longer pelagic larval duration, and higher body condition than fish collected before winter. Lower settlement water temperatures were positively associated with winter survival, indicating that a settlement date closer to the onset of winter was favourable. Additionally, wintered fish, exhibited higher growth rates in early life compared to fish sampled prior to winter onset. These findings suggest that some early life history traits are selected for survival into winter, potentially mediating the physiological impacts of declining water temperature. If such traits increase overwinter survival they may facilitate the establishment of this range-expanding species in temperate rocky reef environments.

Global assessment of manta and devil ray gill plate and meat trade: conservation implications and opportunities - Marta D. Palacios; Laura Weiand; Betty J. L. Laglbauer; Melissa R. Cronin; Sarah Fowler; Rima W. Jabado; Thanda Ko Gyi; Daniel Fernando; Godefroy De Bruyne; Stanley K. H. Shea; Paul Hilton; Yi-Li Gao; et al. (Environmental Biology of Fishes, 2025)

Faster larval growth and shorter pelagic duration enhance the post-settlement persistence of a common range-extending coral-reef fish in a temperate ecosystem - Alexander L. Rigg; Ashley M. Fowler; Ivan Nagelkerken; David J. Booth (Coral Reefs, 2025)
Climate-induced ocean warming facilitates the poleward range expansion of tropical marine species into temperate waters. Such tropicalisation is reshaping marine ecosystems globally and has ecological implications. Our understanding of the factors influencing the establishment and persistence of vagrant tropical species in temperate waters remains limited. To address this knowledge gap, we examined which early life history traits affect the post-settlement persistence of a vagrant tropical fish, the sergeant major damselfish Abudefduf vaigiensis , in temperate waters off southeast Australia. Over an 8-week period, fish were collected, and otolith microstructure analysis indicated that early post-settlement persistence was linked to fast larval growth in the week prior to settlement and to shorter pelagic larval duration, but not body size at hatching or body size at settlement. We conclude that successful invasions of temperate ecosystems by this vagrant tropical fish is likely mediated by demographic advantages these fish gain as early-stage larvae.

Overwintering performance of three juvenile temperate estuarine fishes - Clara Bellotto; Ashley M. Fowler; David J. Booth (Journal of Experimental Marine Biology and Ecology, 2025)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

Biodegradation behavior of wool and other textile fibers in aerobic composting conditions - S. Collie; P. Brorens; M. Hassan; I. Fowler (International Journal of Environmental Science and Technology, 2025)
Pollution of the environment by microscopic fragments of plastic is a growing environmental concern. A category of this pollution is fiber fragments from textiles, a source of which is believed to be fibers released by clothing made of synthetic fibers during laundering. These fragments could enter the environment at the end of the textile’s useful life if it is not re-used or recycled. Disposal of biodegradable fibers could be achieved by industrial composting, but natural fibers are sometimes modified during manufacturing in ways that might influence biodegradation. The composting behavior of fabrics made with unmodified and chemically modified wool fibers (chlorine-Hercosett treated), regenerated cellulose, and several synthetic fibers was compared in industrial composting conditions according to an established standard test method. The fabrics were characterized by Fourier transform infrared spectroscopy, energy dispersive X-ray and electron microscopy. The regenerated cellulose (viscose rayon) biodegraded to the greatest extent in the test, and both types of wool also biodegraded readily. All three synthetic fibers had no biodegradation. The machine-washable wool biodegraded more rapidly than unmodified wool and analysis of residues at the conclusion of the test indicated that it did not generate non-degradable fiber fragments. The epicuticle of unmodified wool is covered with a hydrophobic layer, which may resist microbial attack, but with time this slowly degraded. Conversely, the machine-washable wool is hydrophilic and therefore was easier for microbes to attack. If not re-used, commercial, machine-washable wool textiles can be readily disposed of in industrial composting conditions.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Children’s exposure to chemical contaminants: Demographic disparities and associations with the developing basal ganglia - Carina H. Fowler; Aaron Reuben; Heather M. Stapleton; Kate Hoffman; Nicholas Herkert; Lubna Barakat; Michael S. Gaffrey (Environmental Research, 2024)

Tracing hydrous eclogite melts in the source of sanukitoids - L.M. Spencer; C. Albert; H.M. Williams; O. Nebel; I.J. Parkinson; R.H. Smithies; H. Bruno; M. Fowler; H. Moreira; C.J. Lissenberg; M.-A. Millet (Earth and Planetary Science Letters, 2024)

Hydrocarbon-degrading microbial populations in permanently cold deep-sea sediments in the NW Atlantic - Oyeboade Adebayo; Srijak Bhatnagar; Jamie Webb; Calvin Campbell; Martin Fowler; Natasha M. MacAdam; Adam Macdonald; Carmen Li; Casey R.J. Hubert (Marine Pollution Bulletin, 2024)

Two applications of the Consensus Solutions process with collaborative modeling for management of a contentious oyster fishery - Elizabeth W. North; Michael J. Wilberg; Jeff Blair; Lisa Wainger; Jeffrey C. Cornwell; Robert Jones; Chris Hayes; Rasika Gawde; Raleigh Robert Hood; Taylor Goelz; Troy Hartley; Marvin M. Mace; et al. (Frontiers in Marine Science, 2024)
Worldwide, enhancement of oyster populations is undertaken to achieve a variety of goals including support of food production, local economies, water quality, coastal habitat, biodiversity, and cultural heritage. Although numerous strategies for improving oyster stocks exist, enhancement efforts can be thwarted by long-standing conflict among community groups about which strategies to implement, where efforts should be focused, and how much funding should be allocated to each strategy. The objective of this paper is to compare two engagement approaches that resulted in recommendations for multi-benefit enhancements to oyster populations and the oyster industry in Maryland, U.S.A., using the Consensus Solutions process with collaborative simulation modeling. These recommendations were put forward by the OysterFutures Workgroup in 2018 and the Maryland Oyster Advisory Commission (OAC) in 2021. Notable similarities between the efforts were the basic principles of the Consensus Solutions process: neutral facilitation, a 75% agreement threshold, the presence of management agency leadership at the meetings, a scientific support team that created a management scenario model in collaboration with community group representatives, numerous opportunities for representatives to listen to each other, and a structured consensus building process for idea generation, rating, and approval of management options. To ensure meaningful representation by the most affected user groups, the goal for membership composition was 60% from industry and 40% from advocacy, agency, and academic groups in both processes. Important differences between the processes included the impetus for the process (a research program versus a legislatively-mandated process), the size of the groups, the structure of the meetings, and the clear and pervasive impact of the COVID-19 pandemic on the ability of OAC members to interact. Despite differences and challenges, both groups were able to agree on a package of recommendations, indicating that consensus-based processes with collaborative modeling offer viable paths toward coordinated cross-sector natural resource decisions with scientific basis and community support. In addition, collaborative modeling resulted in ‘myth busting’ findings that allowed participants to reassess and realign their thinking about how the coupled human-oyster system would respond to management changes.

Continued development of a tool to measure intramuscular fat of Australian lamb carcases in commercial situations - Stephanie M. Fowler; Stephen Morris; Suzanne I. Mortimer; David L. Hopkins (Meat Science, 2024)

Tree of life metabarcoding can serve as a biotic benchmark for shifting baselines in urbanized estuaries - Joseph D. DiBattista; Ashley M. Fowler; Tanika C. Shalders; Robert J. Williams; Shaun Wilkinson (Environmental Research, 2024)

Individual performance niches and responses to winter temperature change in three estuarine fishes from eastern Australia - Clara Bellotto; Ashley M. Fowler; David J. Booth (Marine Biology, 2024)
Climate change may impact individual organisms in different ways, a consideration often overshadowed by predominant focus on population effects in studies. We examined three estuarine fish species to determine if individual fish performance, persisted across winter water temperatures. Fish performance at 16 °C (current Sydney winter estuarine water temperature) and 20 °C (predicted under climate change) with low and high food regimes was assessed using key physiological (growth, aerobic scope, burst speed) and behavioural parameters (foraging activity, boldness, shelter usage, predator escape response). We expected a strong positive relationship between performance at 16 °C and 20 °C for each parameter, and interactions with food level, however in general this was not found for any species. Relative performance was only maintained across temperatures for a few parameters, such as bite rate, boldness, and shelter response in one species (trumpeter Pelates sexlineatu s), with aerobic scope in silver biddy Gerres subfasciatus , and boldness in fortescue Centropogon australis . Our results suggest that individuals’ fitness (directly via changes in growth, indirectly via behaviours) might be impacted by climate warming due to differences in relative performance among juvenile individuals across water temperatures. Changes in relative performance among individuals may initially compensate for a population-level response, thereby buffering the effects of climate change.

Validation of Raman spectroscopic models to verify the origin of Australian beef grown under different production systems - Stephanie M. Fowler; Matthew Kerr; David L. Hopkins; Leigh M. Schmidtke (Meat Science, 2024)

The origin and water quality of spring systems in Monchique, Portugal: A focus on Long-Term sustainability and elevated sodium levels - M.A. Hoque; K.B. Amponsah; A. Blum; N. Walton; P. Dennis; A.P. Butler; S. Hugman; A. Bamberger; M. Fowler (Journal of Hydrology, 2024)

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Mineral–water reactions in Earth’s mantle: Predictions from Born theory and ab initio molecular dynamics - Sarah J. Fowler; David M. Sherman; John P. Brodholt; Oliver T. Lord (Geochimica et Cosmochimica Acta, 2024)

Predator-avoidance behaviour of target and non-target temperate reef fishes is lower in areas protected from fishing - David A. Feary; Ashley M. Fowler; David J. Booth (Marine Biology, 2024)
The effects of hunting on predator-avoidance behaviour are increasingly being recognised on land but have received less attention in marine systems. We examined whether predator-avoidance behaviour of temperate reef fishes differed between areas protected and not protected from recreational fishing by examining the flight-initiation distance (FID; the distance a predator can approach before the prey animal flees) of six common species in southeastern Australia. By testing species that ranged in desirability to recreational fishers, we could determine if behavioural differences were specific to target species or extended more broadly throughout the assemblage. After accounting for potential variability among sites within protection levels, we found that the FID of all species was higher in fished areas than protected areas, with FID up to 2.4 times higher in fished areas. The two commonly targeted species had the greatest FID response to fishing. FID also increased with body size for all but one species. Our findings indicate the potential for assemblage-wide effects of fishing on predator-avoidance behaviour and are consistent with an indirect mechanism of behavioural modification.

Staining protocols affect use of otolith to estimate the demography of the damselfish sergeant major ( Abudefduf vaigiensis ) - Alexander L. Rigg; Clara Bellotto; Ashley M. Fowler; David J. Booth (Journal of Fish Biology, 2024)
This study assessed the otolith (sagittae, lapilli, and asterisci) increment deposition rate in the range‐shifting damselfish, A. vaigiensis , using different concentrations of Alizain Red S and evaluated the impact of staining on increment width. Daily increment deposition was verified in all otolith types and presented clearer fluorescent markings in the lapilli and sagittae than the asterisci, with high stain concentration showing the best clarity. Higher stain concentrations were found to decrease increment width, suggesting care is needed when using stained otoliths as a proxy for growth for this species.

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Subtropical coral expansion into SE Australia: a haven for both temperate and expatriating tropical reef fishes - Max J. O’Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Coral Reefs, 2023)
We examined reef fish assemblages in and adjacent to a newly established coral bed (subtropical Pocillopora aliciae ) in temperate south-eastern Australia, to understand whether novel coral habitat is facilitating assemblages of range-expanding tropical and local temperate fishes. This is the first comprehensive assessment of fish species associating with this novel coral habitat within a temperate environment. Twenty fish species were observed associating with the coral (8 tropical and 12 temperate). Both temperate and tropical species were observed at greater (up to 48 times higher) densities on the coral than on nearby temperate rocky reef in the area, suggesting that the corals generally concentrate fish and may aid in tropicalisation for species that use subtropical coral as habitat. Future research should investigate the ongoing expansion of this coral, the relative quality of coral habitat for fish in temperate regions and the potential implications for functioning of temperate rocky reef ecosystems.

Microbial communities are indicators of parasite infection status - Kyle Swanson; April M. H. Blakeslee; Amy E. Fowler; Sara Roozbehi; Erin K. Field (Environmental Microbiology, 2023)
Growing evidence suggests that microbiomes have been shaping the evolutionary pathways of macroorganisms for millennia and that these tiny symbionts can influence, and possibly even control, species interactions like host–parasite relationships. Yet, while studies have investigated host–parasites and microbiomes separately, little has been done to understand all three groups synergistically. Here, we collected infected and uninfected Eurypanopeus depressus crab hosts from a coastal North Carolina oyster reef three times over 4 months. Infected crabs demonstrated an external stage of the rhizocephalan parasite, Loxothylacus panopaei . Community analyses revealed that microbial richness and diversity were significantly different among tissue types (uninfected crab, infected crab, parasite externae and parasite larvae) and over time (summer and fall). Specifically, the microbial communities from parasite externae and larvae had similar microbiomes that were consistent through time. Infected crabs demonstrated microbial communities spanning those of their host and parasite, while uninfected crabs showed more distinctive communities with greater variability over time. Microbial communities were also found to be indicators of early‐stage infections. Resolving the microbial community composition of a host and its parasite is an important step in understanding the microbiome's role in the host–parasite relationship and determining how this tripartite relationship impacts coevolutionary processes.

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Phylogenomics reveals extreme gene tree discordance in a lineage of dominant trees: hybridization, introgression, and incomplete lineage sorting blur deep evolutionary relationships despite clear species groupings in Eucalyptus subgenus Eudesmia - Todd G.B. McLay; Rachael M. Fowler; Patrick S. Fahey; Daniel J. Murphy; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Molecular Phylogenetics and Evolution, 2023)

P16-30: Examining the need for an ovarian-specific steroidogenic assay to prioritize potential endocrine disrupting chemicals - P. Vazakidou; T. Li; L.L. Lecante; S. Mazaud-Guittot; P.A. Fowler; P. Damdimopoulou; P. Leonards; M. van Duursen (Toxicology Letters, 2023)

P08-11: Characterisation of the effects of Ketoconazole on the human fetal adrenal - L.L. Lecante; P. Vazakidou; P. Lelandais; P. Liu; M. van Duursen; S. Mazaud-Guittot; P.A. Fowler (Toxicology Letters, 2023)

The utility of otolith-based methods for discriminating stock structure of the fishery important monacanthid, Nelusetta ayraud, over an intermediate scale - Holly Gunton; Ashley M. Fowler; Marcus E. Miller; David J. Booth; John Stewart (Fisheries Research, 2023)

Multi-criteria analysis for rapid vulnerability assessment of marine species to climate change - Curtis Champion; James R. Lawson; Joanna Pardoe; Derrick O. Cruz; Ashley M. Fowler; Fabrice Jaine; Hayden T. Schilling; Melinda A. Coleman (Climatic Change, 2023)
The accelerating pace of climate-induced stress to global ecosystems threatens the sustainable management and conservation of biodiversity. To effectively respond, researchers and managers require rapid vulnerability assessment tools that can be readily implemented using diverse and existing knowledge sources. Here we demonstrate the application of multi-criteria analysis (MCA) for this purpose using a group of coastal-pelagic fishes from south-eastern Australia as a case-study. We show that MCA has the capacity to formally structure diverse knowledge sources, ranging from peer-reviewed information (which informed 29.2% of criteria among models) to expert knowledge (which informed 22.6% of criteria among models), to quantify the sensitivity of species to biophysical conditions. By integrating MCA models with spatial climate data over historical and future periods, we demonstrate the application of MCA for rapidly assessing the vulnerability of marine species to climate change. Spatial analyses revealed an apparent trend among case-study species towards increasing or stable vulnerability to projected climate change throughout the northern (i.e. equatorward) extent of the study domain and the emergence of climate refugia throughout southern (i.e. poleward) regions. Results from projections using the MCA method were consistent with past analyses of the redistribution of suitable habitat for coastal-pelagic fishes off eastern Australia under climate change. By demonstrating the value of MCA for rapidly assessing the vulnerability of marine species to climate change, we highlight the opportunity to develop user-friendly software infrastructures integrated with marine climate projection data to support the interdisciplinary application of this method.

Internal endpoint temperature (level of cooking doneness) effects on the fatty acid and mineral profiles of grilled lamb m. longissimus lumborum - Benjamin W.B. Holman; Stephanie M. Fowler; Kristy L. Bailes; Richard G. Meyer; David L. Hopkins; Edward H. Clayton (Meat Science, 2023)

Slab-failure or Slab-success? Examining the contributions of crust and mantle to post-subduction magmatism in the Ratagain Complex, NW Scotland - A. Lawrence; M. Fowler; C.G. Kingsbury; T. Knott; Darren Mark; C.T.E. Stevenson (Lithos, 2023)

Attribution of the heavy rainfall events leading to severe flooding in Western Europe during July 2021 - Jordis S. Tradowsky; Sjoukje Y. Philip; Frank Kreienkamp; Sarah F. Kew; Philip Lorenz; Julie Arrighi; Thomas Bettmann; Steven Caluwaerts; Steven C. Chan; Lesley De Cruz; Hylke de Vries; Norbert Demuth; et al. (Climatic Change, 2023)
In July 2021 extreme rainfall across Western Europe caused severe flooding and substantial impacts, including over 200 fatalities and extensive infrastructure damage within Germany and the Benelux countries. After the event, a hydrological assessment and a probabilistic event attribution analysis of rainfall data were initiated and complemented by discussing the vulnerability and exposure context. The global mean surface temperature (GMST) served as a covariate in a generalised extreme value distribution fitted to observational and model data, exploiting the dependence on GMST to estimate how anthropogenic climate change affects the likelihood and severity of extreme events. Rainfall accumulations in Ahr/Erft and the Belgian Meuse catchment vastly exceeded previous observed records. In regions of that limited size the robust estimation of return values and the detection and attribution of rainfall trends are challenging. However, for the larger Western European region it was found that, under current climate conditions, on average one rainfall event of this magnitude can be expected every 400 years at any given location. Consequently, within the entire region, events of similar magnitude are expected to occur more frequently than once in 400 years. Anthropogenic climate change has already increased the intensity of the maximum 1-day rainfall event in the summer season by 3–19 %. The likelihood of such an event to occur today compared to a 1.2 $$^{° }$$ ∘ C cooler climate has increased by a factor of 1.2–9. Models indicate that intensity and frequency of such events will further increase with future global warming. While attribution of small-scale events remains challenging, this study shows that there is a robust increase in the likelihood and severity of rainfall events such as the ones causing extreme impacts in July 2021 when considering a larger region.

Mineral-whole rock isotope fidelity? A comparative study of Hf-Nd-O from high Ba-Sr granitoids - E. Bruand; C. Storey; M. Fowler; B. Dhuime; R. Doucelance (Chemical Geology, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

A newly recorded Cryogenian-Ediacaran Dokhan Volcanic caldera with resurgent uplift in the Arabian-Nubian Shield, southwest Safaga, Egypt - Osama K. Dessouky; Minghai Cai; Hani H. Ali; Ahmed M. Dardier; Abdel-Rahman Fowler; Kamal A. Ali; M. Santosh; Kurt Stüwe; Mahmoud M. Hassan (Precambrian Research, 2023)

Conservation of endangered galaxiid fishes in the Falkland Islands requires urgent action on invasive brown trout - J. F. Minett; D. M. Fowler; J. A. H. Jones; P. Brickle; G. T. Crossin; S. Consuegra; C. Garcia de Leaniz (Biological Invasions, 2023)
Non-native salmonids are protected in the Southern hemisphere where they sustain aquaculture and lucrative sport fisheries, but also impact many native fishes, which poses a conservation conundrum. Legal protection and human-assisted secondary releases may have helped salmonids to spread, but this has seldom been tested. We reconstructed the introduction of brown trout ( Salmo trutta ) to the Falkland Islands using historical records and modelled its dispersal and probability of invasion using a generalized linear model and Leave One out Cross Validation. Our results indicate that establishment success was ~ 88%, and that dispersal was facilitated over land by proximity to invaded sites and density of stream-road crossings, suggesting it was human assisted. Brown trout have already invaded 54% of Falkland rivers, which are 2.9–4.5 times less likely to contain native galaxiids than uninvaded streams. Without strong containment we predict brown trout will invade nearly all suitable freshwater habitats in the Falklands within the next ~ 70 years, which might put native freshwater fishes at a high risk of extinction.

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

The FishPath approach for fisheries management in a data‐ and capacity‐limited world - Natalie A. Dowling; Jono R. Wilson; Jason M. Cope; Dawn T. Dougherty; Serena Lomonico; Carmen Revenga; Brian J. Snouffer; Natalio Godoy Salinas; Felipe Torres‐Cañete; Rowan C. Chick; Ashley M. Fowler; Ana M. Parma (Fish and Fisheries, 2023)
Successful fisheries management systems tend to be underpinned by harvest strategies, specifying formally agreed data collection systems, assessment approaches and management measures used to regulate fishing pressure. While harvest strategies can be effective even in data‐ and capacity‐limited (DCL) situations, their development remains challenging in such contexts. We present a process and decision‐support tool, FishPath, to guide the identification of suitable harvest strategy component options given often debilitating conditions: (i) resource limitations and lack of technical management capacity; (ii) ‘uniqueness’ of DCL fisheries; (iii) the concept of harvest strategies is unfamiliar to managers and scientists, and the universe of options is hard to navigate; and (iv) the lack of an effective participatory process to identify solutions tailored to local contexts. These conditions can lead to either management paralysis or generic solutions that may be poor fits to specific conditions. The FishPath Tool uses a diagnostic questionnaire that elicits the key characteristics and specific circumstances of a fishery. It compares these with the requirements of alternative options from an inventory of possible harvest strategy components, identifies where these requirements are met and provides customised, transparent guidance on the appropriateness of component options of a harvest strategy, specific to the fishery of interest and its governance context. The FishPath Process is a facilitated multi‐stakeholder, participatory engagement process aimed to set fisheries on the path to develop a harvest strategy. The FishPath Process and Tool combine to ensure a bottom‐up, documented, transparent, replicable and efficient process.

Poor utility of environmental DNA for estimating the biomass of a threatened freshwater teleost; but clear direction for future candidate assessments - Meaghan L. Rourke; Jackson Wilkes Walburn; Matt K. Broadhurst; Ashley M. Fowler; Julian M. Hughes; D. Stewart Fielder; Joseph D. DiBattista; Elise M. Furlan (Fisheries Research, 2023)

A microcosm of modern crust formation: Evidence from zircon ages, Hf O and Nd Sr isotopes and bulk geochemistry of the Menglian Batholith, SE Tibet - Ren-Zhi Zhu; Shao-Cong Lai; Mike Fowler; Jin-Cheng Xie; Sarah M. Glynn (Chemical Geology, 2023)

Hydroacoustic surveys reveal the distribution of mid-water fish around two artificial reef designs in temperate Australia - Alistair Becker; Michael B. Lowry; Ashley M. Fowler; Matthew D. Taylor (Fisheries Research, 2023)

Mouse organoids as an in vitro tool to study the in vivo intestinal response to cytotoxicants - F. Jardi; C. Kelly; C. Teague; H. Fowler-Williams; D. C. Sevin; D. Rodrigues; H. Jo; S. Ferreira; B. Herpers; M. Van Heerden; T. de Kok; C. Pin; et al. (Archives of Toxicology, 2023)

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda - Weston M. Eaton; Morey Burnham; Tahnee Robertson; J. G. Arbuckle; Kathryn J. Brasier; Mark E. Burbach; Sarah P. Church; Georgia Hart-Fredeluces; Douglas Jackson-Smith; Grace Wildermuth; Katherine N. Canfield; S. Carolina Córdova; et al. (Socio-Ecological Practice Research, 2022)
Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusion interests through engagement, while implied in key conceptual frameworks, remain underexplored in scholarly work and collaborative practice alike. A second line of inquiry relates to research–practice gaps. While both the practice of doing engagement work and scholarly research on the efficacy of engagement is on the rise, there is little concerted interplay among ‘on-the-ground’ practitioners and scholarly researchers. This means scientific research often misses or ignores insight grounded in practical and experiential knowledge, while practitioners are disconnected from potentially useful scientific research on stakeholder engagement. A third set of questions concerns gaps in empirical understanding of the efficacy of engagement processes and includes inquiry into how different engagement contexts and process features affect a range of behavioral, cognitive, and decision-making outcomes. Because of these gaps, a cohesive and actionable research agenda for stakeholder engagement research and practice in working landscapes remains elusive. In this review article, we present a co-produced research agenda for stakeholder engagement in working landscapes. The co-production process involved professionally facilitated and iterative dialogue among a diverse and international group of over 160 scholars and practitioners through a yearlong virtual workshop series. The resulting research agenda is organized under six cross-cutting themes: (1) Justice, Equity, Diversity, and Inclusion; (2) Ethics; (3) Research and Practice; (4) Context; (5) Process; and (6) Outcomes and Measurement. This research agenda identifies critical research needs and opportunities relevant for researchers, practitioners, and policymakers alike. We argue that addressing these research opportunities is necessary to advance knowledge and practice of stakeholder engagement and to support more just and effective engagement processes in working landscapes.

Putting sharks on the map: A global standard for improving shark area-based conservation - Ciaran A. Hyde; Giuseppe Notarbartolo di Sciara; Lynn Sorrentino; Charlotte Boyd; Brittany Finucci; Sarah L. Fowler; Peter M. Kyne; Guido Leurs; Colin A. Simpfendorfer; Michael J. Tetley; Freya Womersley; Rima W. Jabado (Frontiers in Marine Science, 2022)
Area-based conservation is essential to safeguard declining biodiversity. Several approaches have been developed for identifying networks of globally important areas based on the delineation of sites or seascapes of importance for various elements of biodiversity (e.g., birds, marine mammals). Sharks, rays, and chimaeras are facing a biodiversity crisis with an estimated 37% of species threatened with extinction driven by overfishing. Yet spatial planning tools often fail to consider the habitat needs critical for their survival. The Important Shark and Ray Area (ISRA) approach is proposed as a response to the dire global status of sharks, rays, and chimaeras. A set of four globally standardized scientific criteria, with seven sub-criteria, was developed based on input collated during four shark, biodiversity, and policy expert workshops conducted in 2022. The ISRA Criteria provide a framework to identify discrete, three-dimensional portions of habitat important for one or more shark, ray, or chimaera species, that have the potential to be delineated and managed for conservation. The ISRA Criteria can be applied to all environments where sharks occur (marine, estuarine, and freshwater) and consider the diversity of species, their complex behaviors and ecology, and biological needs. The identification of ISRAs will guide the development, design, and application of area-based conservation initiatives for sharks, rays, and chimaeras, and contribute to their recovery.

Habitat value of subsea wells and pipelines for fishery target species in Australia - Dianne McLean; Conrad W. Speed; Matthew Jon Birt; Jamie Colquhoun; Mark Case; Marcus Stowar; Todd Bond; Daniel Ierodiaconou; Sasha K. Whitmarsh; Michael D. Taylor; Sam Wines; David John Booth; et al. (Frontiers in Marine Science, 2022)
Subsea pipelines and wells installed to support the oil and gas industry represent some of the most extensive and numerous anthropogenic structures throughout global marine ecosystems. There remains a paucity of information on the habitat value of these structures for fishery target species and, as a result, little understanding of how decommissioning should be conducted to minimise impacts to populations of these economically and socially important species. We assess the diversity and abundance of species that are targets of recreational and commercial fisheries on 33 subsea wells and 17 pipelines across the tropical northwest and temperate southeast marine regions of Australia. We examine relationships between fish identity and abundance and a range of environmental (e.g., depth, location), infrastructure-specific (e.g., pipeline position, diameter, age, length of pipeline, height of well, position on well), and biological (% cover of epibiota) variables using video filmed by remotely operated vehicles during their routine offshore inspection and maintenance campaigns. A total of 100 fishery target species were observed across subsea well and pipeline infrastructure, 56 species uniquely observed on pipelines and nine unique to wells. The families Lutjanidae (snapper), Serranidae (rock cods, groupers, perch), and Carangidae (trevallies) were most common and abundant on both wells and pipelines. In the northwest, lutjanids were most abundant around the base of wells, in shallow depths, on shorter wells, and where pipelines spanned the seafloor. A greater number of fishery target species and abundance of ocean perch ( Helicolenus spp.) were also associated with pipelines that spanned the seafloor in temperate southeast Australia. The combined biomass of three species of snapper on wells in the northwest was 1,270 kg, with production levels for these species on each well estimated to be 105.2 g m 2 year -1 . The present study serves as an important reference point for informing decommissioning decisions for pipeline and well infrastructure and demonstrates the utility of industry-held data for science. We suggest that key predictor variables identified here be incorporated into comprehensive before-after-control-impact scientific studies for specific fields/assets to enable the prediction of potential impacts of decommissioning scenarios on marine communities present and quantification of such impacts after the decommissioning activity has occurred.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Recruiting a long way from home: Domino damselfish Dascyllus trimaculatus can detect new temperate coral habitat and conspecifics - Max J. O'Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Journal of Fish Biology, 2022)
Climate change is driving tropicalisation of temperate reefs, yet it is unclear how range‐shifting tropical fishes locate suitable habitat. The authors tested whether juvenile tropical damsels Dascyllus trimaculatus could detect rare coral habitat ( Pocillopora aliciae ) and conspecifics on temperate rocky reefs using olfactory and visual preference experiments. For all cues, individuals selected and spent more time than expected in aquarium areas with the cue present, which included coral odour and conspecific odour and visual cues. This indicates that vagrant coral‐reef fish can detect rare suitable habitat outside of their natal range.

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Extreme windstorms and sting jets in convection-permitting climate simulations over Europe - Colin Manning; Elizabeth J. Kendon; Hayley J. Fowler; Nigel M. Roberts; Ségolène Berthou; Dan Suri; Malcolm J. Roberts (Climate Dynamics, 2022)
Extra-tropical windstorms are one of the costliest natural hazards affecting Europe, and windstorms that develop a sting jet are extremely damaging. A sting jet is a mesoscale core of very high wind speeds that occurs in Shapiro–Keyser type cyclones, and high-resolution models are required to adequately model sting jets. Here, we develop a low-cost methodology to automatically detect sting jets, using the characteristic warm seclusion of Shapiro–Keyser cyclones and the slantwise descent of high wind speeds, within pan-European 2.2 km convection-permitting climate model (CPM) simulations. The representation of wind gusts is improved with respect to ERA-Interim reanalysis data compared to observations; this is linked to better representation of cold conveyor belts and sting jets in the CPM. Our analysis indicates that Shapiro–Keyser cyclones, and those that develop sting jets, are the most damaging windstorms in present and future climates. The frequency of extreme windstorms is projected to increase by 2100 and a large contribution comes from sting jet storms. Furthermore, extreme wind speeds and their future changes are underestimated in the global climate model (GCM) compared to the CPM. We conclude that the CPM adds value in the representation of extreme winds and surface wind gusts and can provide improved input for impact models compared to coarser resolution models.

Native tube-building polychaete prefers to anchor non-native alga over other macrophytes - Alexander W. Mott; Stacy A. Krueger-Hadfield; April M. H. Blakeslee; Amy E. Fowler (Oecologia, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Use of plastid genome sequences in phylogeographic studies of tree species can be misleading without comprehensive sampling of co-occurring, related species - Patrick S. Fahey; Rachael M. Fowler; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Tree Genetics & Genomes, 2021)

Pharmacokinetic and pharmacodynamic properties of aerosolized (“vaped”) THC in adolescent male and female rats - C. M. Ruiz; A. Torrens; V. Lallai; E. Castillo; L. Manca; M. X. Martinez; D. N. Justeson; C. D. Fowler; D. Piomelli; S. V. Mahler (Psychopharmacology, 2021)

Marginal support for a trophic cascade among sympatric canids in peripheral wolf range - Nicholas L. Fowler; Todd M. Kautz; Tyler R. Petroelje; Clay M. Wilton; Kenneth F. Kellner; Daniel J. O’Brien; Bill Parsons; Dean E. Beyer; Jerrold L. Belant (Ecology, 2021)
Trophic cascades reportedly structure ecological communities through indirect species interactions. Though the predator–herbivore–autotroph relationship has received much attention, mechanistic evidence supporting intraguild trophic cascades is rare. We established 348 remote camera sites (1 August–5 September 2019) across seven study areas of varying wolf ( Canis lupus ) density including one study area where wolves were absent in northern Michigan, USA. Using multi‐species occupancy modeling at species‐relevant spatial scales, we evaluated the hypothesis that increased wolf occurrence suppresses coyote ( C . latrans ) occurrence with corresponding increased red fox ( Vulpes vulpes ) occurrence mediated by land cover edge density, human presence, and temporal partitioning. Remote cameras recorded >600,000 images and included 6,370, 10,137, and 4,876 detections of wolves, coyotes, and foxes, respectively. Fox occupancy probability was more than three times as high (0.29) at camera sites where wolves were present, relative to sites wolves were absent (0.09). Pairwise species interactions supported expected size‐based dominance patterns among canids and insignificant effects were directionally consistent with reported reduced strength of top‐down effects in peripheral wolf range. Increased edge density also increased co‐occurrence of coyote and wolves, likely a function of increased prey availability and refugia for coyotes. Though foxes occurred in spatial proximity to wolves, competition was limited by greater temporal partitioning than observed between coyotes and foxes that were spatially segregated. Collectively, our results provide marginal support for the reported trophic cascade among wolves, coyotes, and foxes wherein top‐down effects may be reduced near the edge of current wolf distributions. As predators continue to recolonize portions of their historic range, knowledge of the effects on intraguild predators has implications for species management and predicting prey population responses.

Invasion history shapes host transcriptomic response to a body‐snatching parasite - Zachary J. C. Tobias; Amy E. Fowler; April M. H. Blakeslee; John A. Darling; Mark E. Torchin; A. Whitman Miller; Gregory M. Ruiz; Carolyn K. Tepolt (Molecular Ecology, 2021)
By shuffling biogeographical distributions, biological invasions can both disrupt long‐standing associations between hosts and parasites and establish new ones. This creates natural experiments with which to study the ecology and evolution of host–parasite interactions. In estuaries of the Gulf of Mexico, the white‐fingered mud crab ( Rhithropanopeus harrisii ) is infected by a native parasitic barnacle, Loxothylacus panopaei (Rhizocephala), which manipulates host physiology and behaviour. In the 1960s, L . panopaei was introduced to the Chesapeake Bay and has since expanded along the southeastern Atlantic coast, while host populations in the northeast have so far been spared. We use this system to test the host's transcriptomic response to parasitic infection and investigate how this response varies with the parasite's invasion history, comparing populations representing (i) long‐term sympatry between host and parasite, (ii) new associations where the parasite has invaded during the last 60 years and (iii) naïve hosts without prior exposure. A comparison of parasitized and control crabs revealed a core response, with widespread downregulation of transcripts involved in immunity and moulting. The transcriptional response differed between hosts from the parasite's native range and where it is absent, consistent with previous observations of increased susceptibility in populations lacking exposure to the parasite. Crabs from the parasite's introduced range, where prevalence is highest, displayed the most dissimilar response, possibly reflecting immune priming. These results provide molecular evidence for parasitic manipulation of host phenotype and the role of gene regulation in mediating host–parasite interactions.

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

Molecular characterization of clinical carbapenem-resistant Enterobacterales from Qatar - Fatma Ben Abid; Clement K. M. Tsui; Yohei Doi; Anand Deshmukh; Christi L. McElheny; William C. Bachman; Erin L. Fowler; Ahmed Albishawi; Kamran Mushtaq; Emad B. Ibrahim; Sanjay H. Doiphode; Manal M. Hamed; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
One hundred forty-nine carbapenem-resistant Enterobacterales from clinical samples obtained between April 2014 and November 2017 were subjected to whole genome sequencing and multi-locus sequence typing. Klebsiella pneumoniae (81, 54.4%) and Escherichia coli (38, 25.5%) were the most common species. Genes encoding metallo-β-lactamases were detected in 68 (45.8%) isolates, and OXA-48-like enzymes in 60 (40.3%). bla NDM-1 (45; 30.2%) and bla OXA-48 (29; 19.5%) were the most frequent. KPC-encoding genes were identified in 5 (3.6%) isolates. Most common sequence types were E. coli ST410 (8; 21.1%) and ST38 (7; 18.4%), and K. pneumoniae ST147 (13; 16%) and ST231 (7; 8.6%).

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Growth impacts in a changing ocean: insights from two coral reef fishes in an extreme environment - Daniele D’Agostino; John A. Burt; Veronica Santinelli; Grace O. Vaughan; Ashley M. Fowler; Tom Reader; Brett M. Taylor; Andrew S. Hoey; Geórgenes H. Cavalcante; Andrew G. Bauman; David A. Feary (Coral Reefs, 2021)
Determining the life-history consequences for fishes living in extreme and variable environments will be vital in predicting the likely impacts of ongoing climate change on reef fish demography. Here, we compare size-at-age and maximum body size of two common reef fish species ( Lutjanus ehrenbergii and Pomacanthus maculosus ) between the environmentally extreme Arabian/Persian Gulf (‘Arabian Gulf’) and adjacent comparably benign Oman Sea. Additionally, we use otolith increment width profiles to investigate the influence of temperature, salinity and productivity on the individual growth rates. Individuals of both species showed smaller size-at-age and lower maximum size in the Arabian Gulf compared to conspecifics in the less extreme and less variable environment of the Oman Sea, suggesting a life-history trade-off between size and metabolic demands. Salinity was the best environmental predictor of interannual growth across species and regions, with low growth corresponding to more saline conditions. However, salinity had a weaker negative effect on interannual growth of fishes in the Arabian Gulf than in the Oman Sea, indicating Arabian Gulf populations may be better able to acclimate to changing environmental conditions. Temperature had a weak positive effect on the interannual growth of fishes in the Arabian Gulf, suggesting that these populations may still be living within their thermal windows. Our results highlight the potential importance of osmoregulatory cost in impacting growth, and the need to consider the effect of multiple stressors when investigating the consequences of future climate change on fish demography.

New hourly extreme precipitation regions and regional annual probability estimates for the UK - Motasem M. Darwish; Mari R. Tye; Andreas F. Prein; Hayley J. Fowler; Stephen Blenkinsop; Murray Dale; Duncan Faulkner (International Journal of Climatology, 2021)
Recent flooding related to extreme precipitation in the UK has highlighted the importance of better understanding these events. Many studies have quantified annual exceedance probabilities (or return periods) for UK extreme daily precipitation using fixed regions (e.g., HadUKP) and region of interest (ROI) (e.g., Flood Estimation Handbook) approaches, although fewer have evaluated short‐duration events, which are important for flash flooding. Existing UK extreme precipitation regions are based on daily datasets which have different characteristics compared to sub‐daily extremes, and their application to quantify short‐duration extremes may therefore be inappropriate. We use a recently available, quality‐controlled hourly precipitation dataset for the UK from 1992 to 2014 to derive various extreme precipitation indices (e.g., annual maxima, 0.99 quantile) which are combined with additional climatological variables (e.g., temperature), geographical characteristics (e.g., latitude), and weather patterns (WPs) to characterize the UK hourly extreme precipitation climatology and to define five new hourly extreme regions. These regions fulfil regional homogeneity and discordancy statistical measures, and reflect the dynamical processes associated with the weather pattern categorisation defined over the UK and surrounding European area. Thereafter, we use regional frequency analysis (RFA) to fit generalized extreme value (GEV) and generalized Pareto (GP) distributions to 1 hr annual maxima (AMAX) and 0.99 quantile (Q99) precipitation, respectively, to calculate regional annual probability estimates (AEP) for 20%, 10%, and 2% (i.e., 5‐, 10‐, and 50‐year return periods). The new regions capture the spatial variation of hourly precipitation across the UK. Furthermore, the AEP estimates using both distributions are similar for each region. Finally, the WPs associated with the frequency and intensity of the most extreme hourly precipitation accumulations are not identical to results reported by others for daily precipitation.

Using a biophysical model to investigate connectivity between spawning grounds and nursery areas of King George whiting ( Sillaginodes punctatus : Perciformes) in South Australia’s gulfs - Troy A. Rogers; Ana Redondo Rodriguez; Anthony J. Fowler; Mark J. Doubell; Michael J. Drew; Michael A. Steer; Damian Matthews; Charles James; Bronwyn M. Gillanders (Fisheries Oceanography, 2021)
Many demersal marine fish species depend on a dispersive larval stage that connects geographically discrete sub‐populations. Understanding connectivity between these sub‐populations is necessary to determine stock structure, which identifies the appropriate spatial scale for fishery management. Such connectivity is poorly understood for King George whiting ( Sillaginodes punctatus ; Perciformes) in South Australia's gulf system, even though spawning grounds and nursery areas are adequately defined. In response to declines in commercial catches and estimated biomass, this study aimed to determine the most important spawning grounds and nursery areas to recruitment, and the connectivity between them. A biophysical model was seeded with particles according to the distribution and density of eggs throughout the spawning area in 2017 and 2018. Despite inter‐annual differences in the origins of particles, dispersal pathways and predicted settlement areas remained consistent between years. Predicted settlement was generally highest to nursery areas only short distances from regional spawning grounds, consistent with previous hydrodynamic models. However, the model also predicted that spawning in one region could contribute to recruitment in an adjacent region later in the spawning season, which aligned with the breakdown of thermohaline fronts at the entrance of each gulf. The connectivity between spawning grounds and nursery areas predicted by the model is supported by spatio‐temporal patterns in the otolith chemistry of pre‐flexion larvae and settled juveniles. Consequently, the most parsimonious explanation is that the populations of King George whiting in South Australia's gulf system constitute a single, panmictic stock, which has implications for fishery management.

Complement levels in patients with bloodstream infection due to Staphylococcus aureus or Gram-negative bacteria - Emily M. Eichenberger; Michael Dagher; Felicia Ruffin; Lawrence Park; Lisa Hersh; Sumathi Sivapalasingam; Vance G. Fowler; Brinda C. Prasad (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Strong genetic structure in a widespread estuarine crab: A test of potential versus realized dispersal - Carolyn K. Tepolt; April M. H. Blakeslee; Amy E. Fowler; John A. Darling; Mark E. Torchin; A. Whitman Miller; Gregory M. Ruiz (Journal of Biogeography, 2020)
Aim Genetic structure has proven difficult to predict for marine and estuarine species with multi‐day pelagic larval durations, since many disperse far less than expected based on passive transport models. In such cases, the gap between potential and realized dispersal may result from larval behaviours that evolved to facilitate retention and settlement in favourable environments. Behaviour is predicted to play a particularly key role in structuring truly estuarine species, which often moderate their behaviour to remain within their natal estuaries. In such systems, this restricted dispersal may lead to high divergence, local adaptation and eventual speciation across their range. Here, we test whether a geographically widespread estuarine crab, known to have behaviour promoting larval retention, exhibits high population structure despite a 2‐ to 4‐week larval duration. Location Atlantic and Gulf Coasts of North America. Taxon White‐fingered mud crab, Rhithropanopeus harrisii . Methods Population genomic analyses across nine estuaries from New Hampshire to Louisiana using 12,638 transcriptome‐derived SNPs. Results We found highly differentiated genetic signatures among all nine estuaries, separated by 200–5,000 km of coastline. Estimates of gene flow suggest that migration is low and largely symmetrical between sites. We also observed deep phylogenetic divides corresponding to major biogeographical breaks. Main conclusions These results indicate substantial and longstanding constraints to dispersal in the species’ native range, likely arising from the emergence of geological and oceanographic barriers and sustained by behaviour that promotes estuarine retention during larval development. This work supports the idea that larval behaviour promoting estuarine retention can be reflected in substantial genetic structure even in species with multi‐week pelagic larval durations. Such behaviour‐restricted dispersal has implications for predicting adaptation and spread in estuarine species, many of which have been introduced outside their native ranges.

Putative adverse outcome pathways for female reproductive disorders to improve testing and regulation of chemicals - Hanna K. L. Johansson; Pauliina Damdimopoulou; Majorie B. M. van Duursen; Julie Boberg; Delphine Franssen; Marijke de Cock; Kersti Jääger; Magdalena Wagner; Agne Velthut-Meikas; Yuling Xie; Lisa Connolly; Pauline Lelandais; et al. (Archives of Toxicology, 2020)
Modern living challenges female reproductive health. We are witnessing a rise in reproductive disorders and drop in birth rates across the world. The reasons for these manifestations are multifaceted and most likely include continuous exposure to an ever-increasing number of chemicals. The cause–effect relationships between chemical exposure and female reproductive disorders, however, have proven problematic to determine. This has made it difficult to assess the risks chemical exposures pose to a woman’s reproductive development and function. To address this challenge, this review uses the adverse outcome pathway (AOP) concept to summarize current knowledge about how chemical exposure can affect female reproductive health. We have a special focus on effects on the ovaries, since they are essential for lifelong reproductive health in women, being the source of both oocytes and several reproductive hormones, including sex steroids. The AOP framework is widely accepted as a new tool for toxicological safety assessment that enables better use of mechanistic knowledge for regulatory purposes. AOPs equip assessors and regulators with a pragmatic network of linear cause–effect relationships, enabling the use of a wider range of test method data in chemical risk assessment and regulation. Based on current knowledge, we propose ten putative AOPs relevant for female reproductive disorders that can be further elaborated and potentially be included in the AOPwiki. This effort is an important step towards better safeguarding the reproductive health of all girls and women.

Calbindin Deficits May Underlie Dissociable Effects of 5-HT6 and mGlu7 Antagonists on Glutamate and Cognition in a Dual-Hit Neurodevelopmental Model for Schizophrenia - Sinead E. Shortall; Angus M. Brown; Eliot Newton-Mann; Erin Dawe-Lane; Chanelle Evans; Maxine Fowler; Madeleine V. King (Molecular Neurobiology, 2020)
Despite several compounds entering clinical trials for the negative and cognitive symptoms of schizophrenia, few have progressed beyond phase III. This is partly attributed to a need for improved preclinical models, to understand disease and enable predictive evaluation of novel therapeutics. To this end, one recent approach incorporates “dual-hit” neurodevelopmental insults like neonatal phencyclidine plus isolation rearing (PCP-Iso). Glutamatergic dysfunction contributes to schizophrenia pathophysiology and may represent a treatment target, so we used enzyme-based microsensors to evaluate basal- and drug-evoked glutamate release in hippocampal slices from rats that received neonatal PCP and/or isolation rearing. 5-HT 6 antagonist-evoked glutamate release (thought to be mediated indirectly via GABAergic disinhibition) was reduced in PCP-Iso, as were cognitive effects of a 5-HT 6 antagonist in a hippocampal glutamate-dependent novel object discrimination task. Yet mGlu 7 antagonist-evoked glutamatergic and cognitive responses were spared. Immunohistochemical analyses suggest these findings (which mirror the apparent lack of clinical response to 5-HT 6 antagonists in schizophrenia) are not due to reduced hippocampal 5-HT input in PCP-Iso, but may be explained by reduced calbindin expression. This calcium-binding protein is present in a subset of GABAergic interneurons receiving preferential 5-HT innervation and expressing 5-HT 6 receptors. Its loss (in schizophrenia and PCP-Iso) would be expected to reduce interneuron firing and potentially prevent further 5-HT 6 antagonist-mediated disinhibition, without impacting on responses of VIP-expressing interneurons to mGlu 7 antagonism. This research highlights the importance of improved understanding for selection of appropriate preclinical models, especially where disease neurobiology impacts on cells mediating the effects of potential therapeutics.

Assessing Chemical Mechanisms Underlying the Effects of Sunflower Pollen on a Gut Pathogen in Bumble Bees - Lynn S. Adler; Alison E. Fowler; Rosemary L. Malfi; Patrick R. Anderson; Lily M. Coppinger; Pheobe M. Deneen; Stephanie Lopez; Rebecca E. Irwin; Iain W. Farrell; Philip C. Stevenson (Journal of Chemical Ecology, 2020)

Accidental associates are not symbionts: the absence of a non-parasitic endosymbiotic community inside the common periwinkle Littorina littorea (Mollusca: Gastropoda) - James T. Carlton; April M. H. Blakeslee; Amy E. Fowler (Marine Biology, 2020)

Social structure of killer whales ( Orcinus orca ) in a variable low‐latitude environment, the Galápagos Archipelago - Judith Denkinger; Daniela Alarcon; Bitinia Espinosa; Lynn Fowler; Cindy Manning; Javier Oña; Daniel M. Palacios (Marine Mammal Science, 2020)
Killer whales ( Orcinus orca ) have strong social matrilineal bonds and form groups and long‐lasting associations, but little is known about their population or social structure in an equatorial setting such as the waters around the Galápagos Islands. Using 91 encounters and identification photographs from 1991 to 2017, we identified 64 killer whales of which 18 individuals were locals with high resighting rates. Group size was small, ranging from 1 to 15 animals, with 69% of the groups containing four or fewer animals. Using social network analysis (SOCPROG 2.7) whales grouped into three distinct units and one loose association with frequent exchange between different groups. One male–male unit showed a strong association (association strength = 0.55). Overall, associations lasted over at least 3 years. Our data give first evidence of a loose social organization of Galápagos killer whales, similar to fission‐fusion societies.

Plastid phylogenomic analysis of tribe Myoporeae (Scrophulariaceae) - Rachael M. Fowler; Todd G. B. McLay; Tanja M. Schuster; Bevan J. Buirchell; Daniel J. Murphy; Michael J. Bayly (Plant Systematics and Evolution, 2020)

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Insights into fish auditory structure–function relationships from morphological and behavioural ontogeny in a maturing sciaenid - Matthew D. Taylor; Ashley M. Fowler; Iain M. Suthers (Marine Biology, 2020)

Discriminating Natal Source Populations of a Temperate Marine Fish Using Larval Otolith Chemistry - Troy A. Rogers; Anthony J. Fowler; Michael A. Steer; Bronwyn M. Gillanders (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Galactitol catabolism in Sinorhizobium meliloti is dependent on a chromosomally encoded sorbitol dehydrogenase and a pSymB-encoded operon necessary for tagatose catabolism - MacLean G. Kohlmeier; Catherine E. White; Jane E. Fowler; Turlough M. Finan; Ivan J. Oresnik (Molecular Genetics and Genomics, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

The colour of environmental fluctuations associated with terrestrial animal population dynamics - David Gilljam; Jonas Knape; Andreas Lindén; Marianne Mugabo; Steven M. Sait; Mike S. Fowler (Global Ecology and Biogeography, 2019)
Aim The temporal structure (colour) of environmental variation influences population fluctuations, extinction risk and community stability. However, it is unclear whether environmental covariates linked to population fluctuations are distinguishable from a purely random process (white noise). We aimed to estimate colour coefficients and relative support for three models commonly representing coloured stochastic processes, in environmental series linked to terrestrial animal population fluctuations. Location North America and Eurasia. Time period 1901–2002. Major taxa studied Birds, insects and mammals. Methods We analysed multiple abiotic environmental covariates, comparing point estimates and confidence intervals of temporal structure in competing models fitted using white noise, autoregressive [AR(1)] and 1/ f processes in the time domain and the frequency domain (where time series were analysed after decomposition into different sinusoidal frequencies and their relative powers). All animal time series were sampled annually for ≤ 50 years, potentially inflating type II errors. We also considered 101‐year series of matched environmental covariates, performing a statistical power analysis evaluating our ability to draw robust conclusions. Results Temperature‐related variables were associated with the largest fraction of population fluctuations. Ninety‐three per cent of shorter environmental series were indistinguishable from white noise, limited by time‐series length and associated with wide confidence intervals. The longer environmental series analysed in the time domain offered sufficiently high statistical power to identify correctly colour estimates ≥ |0.27|, indicating that 20% of series were best described by a slightly reddened noise process. Main conclusions Focusing on the short time‐scales typically available for ecologists, most environmental variables associated with terrestrial animal population fluctuations are best characterized by white noise processes, although type II errors are common. The correct detection of intermediately coloured noise with power 0.8 requires ≥ 16 data points in the time domain or ≥ 47 points in the frequency domain. Over longer time‐scales, where type II errors are less likely, one‐fifth of populations are associated with coloured (often reddened) variables.

Some Old Movies Become Classics – A Case Study Determining the Scientific Value of ROV Inspection Footage on a Platform on Australia’s North West Shelf - Paul G. Thomson; Ashley M. Fowler; Andrew R. Davis; Charitha B. Pattiaratchi; David J. Booth (Frontiers in Marine Science, 2018)

Storylines: an alternative approach to representing uncertainty in physical aspects of climate change - Theodore G. Shepherd; Emily Boyd; Raphael A. Calel; Sandra C. Chapman; Suraje Dessai; Ioana M. Dima-West; Hayley J. Fowler; Rachel James; Douglas Maraun; Olivia Martius; Catherine A. Senior; Adam H. Sobel; et al. (Climatic Change, 2018)

Multifunctional roles of tropomodulin-3 in regulating actin dynamics - Justin Parreno; Velia M. Fowler (Biophysical Reviews, 2018)

New poleward observations of 30 tropical reef fishes in temperate southeastern Australia - Ashley M. Fowler; Kerryn Parkinson; David J. Booth (Marine Biodiversity, 2018)

A regional frequency analysis of UK sub‐daily extreme precipitation and assessment of their seasonality - Motasem M. Darwish; Hayley J. Fowler; Stephen Blenkinsop; Mari R. Tye (International Journal of Climatology, 2018)
Floods related to extreme precipitation events, especially intense, short‐duration precipitation, may cause significant damage in urbanized areas, including transport infrastructure, electricity networks, and property. These events are expected to increase in frequency with climate change but their characteristics, at either hourly or multi‐hourly timescales, have been little studied due to short and poor quality data records. We examine annual maximum (AMAX) hourly and multi‐hourly (3, 6, 12, and 24 hr) precipitation accumulations in the United Kingdom using a quality‐controlled hourly precipitation data set for the period 1992–2014. We describe their seasonality and diurnal cycle and use a regional frequency analysis (RFA) approach with L ‐moments to produce at‐site return level estimates, and then use existing extreme precipitation regions to provide regional‐scale return levels. The analysis shows a clear seasonality and the dominant occurrence of short‐duration AMAX in summer with similar seasonality for 1 and 3 hr accumulation periods in some regions, while longer‐duration AMAX (12 and 24 hr) behave similarly to each other in all regions but are distributed over a longer period including late autumn and winter. The diurnal cycle of 1 hr AMAX indicates that most extremes occur during the afternoon, with a peak typically between 1400 and 1700, especially in southern and eastern regions. However, we also demonstrate that existing regions for UK daily extremes are not able to adequately reflect differences at shorter durations and that new regions should be created. These results provide new insights to help in designing urban drainage systems and infrastructure, including the need for new scaling relationships between sub‐daily and design accumulation periods.

Characterization of Behavioral, Signaling and Cytokine Alterations in a Rat Neurodevelopmental Model for Schizophrenia, and Their Reversal by the 5-HT6 Receptor Antagonist SB-399885 - Sinead E. Shortall; Ola H. Negm; Maxine Fowler; Lucy C. Fairclough; Patrick J. Tighe; Peter M. Wigmore; Madeleine V. King (Molecular Neurobiology, 2018)

Pilot Test of Survey to Assess Dental and Dental Hygiene Student Human Papillomavirus-Related Oropharyngeal Cancer Knowledge, Perceptions, and Clinical Practices - Holdunn Rutkoski; Brynn Fowler; Ryan Mooney; Lisa Pappas; Barbara L. Dixon; Lilliam M. Pinzon; James Winkler; Deanna Kepka (Journal of Cancer Education, 2018)

Statistics of multi‐year droughts from the method for object‐based diagnostic evaluation - Abayomi A. Abatan; William J. Gutowski; Caspar M. Ammann; Laurna Kaatz; Barbara G. Brown; Lawrence Buja; Randy Bullock; Tressa Fowler; Eric Gilleland; John Halley Gotway (International Journal of Climatology, 2018)
This study uses the method for object‐based diagnostic evaluation (MODE) technique to examine and compare the statistics of drought attributes over the upper Colorado River basin (UCRB). The drought objects are based on the standardized precipitation index (SPI) and the standardized precipitation evapotranspiration index (SPEI) on a 36‐month timescale (SPI36 and SPEI36, respectively). The drought indicators are calculated using monthly precipitation as well as minimum and maximum temperatures from the Precipitation–Elevation Regression on Independent Slopes Model data sets from 1948 to 2012. MODE uses paired object attributes such as centroid distance, orientation angle, area ratio, and intersection area and a combination of parameter thresholds to determine the number of objects identified and retained in the merging and matching process in the two fields. Using MODE run with convolution radius of zero (no smoothing) and an area threshold of four grid points, this study computes and analyses object statistics including centroid locations, areas, and intensity percentiles. Results of the analysis show that SPI36 produces more drought objects than SPEI36. Although the spatial patterns are roughly similar leading up to almost similar statistics of object attributes, such as locations of the object centroids, the SPI36 produces higher percentile intensity of drought objects than does SPEI36, which is clearly obvious in the 90th percentile intensity of drought objects. The largest difference between SPEI36 and SPI36 occurs in the area of drought objects during the early 2000s when the region experienced multi‐year drought resulting from increased warming of the atmosphere. This study demonstrates the use of MODE as a tool to evaluate and monitor drought event over the UCRB.

Relationships Between Meteorological and Water Quality Variables and Fisheries-Independent White Shrimp (Litopenaeus setiferus) Catch in the ACE Basin NERR, South Carolina - Amy E. Fowler; John W. Leffler; Sharleen P. Johnson; Lawrence B. DeLancey; Denise M. Sanger (Estuaries and Coasts, 2018)

Familial social structure and socially driven genetic differentiation in Hawaiian short‐finned pilot whales - Amy M. Van Cise; Karen. K. Martien; Sabre D. Mahaffy; Robin W. Baird; Daniel L. Webster; James H. Fowler; Erin M. Oleson; Phillip A. Morin (Molecular Ecology, 2017)
Social structure can have a significant impact on divergence and evolution within species, especially in the marine environment, which has few environmental boundaries to dispersal. On the other hand, genetic structure can affect social structure in many species, through an individual preference towards associating with relatives. One social species, the short‐finned pilot whale ( Globicephala macrorhynchus ), has been shown to live in stable social groups for periods of at least a decade. Using mitochondrial control sequences from 242 individuals and single nucleotide polymorphisms from 106 individuals, we examine population structure among geographic and social groups of short‐finned pilot whales in the Hawaiian Islands, and test for links between social and genetic structure. Our results show that there are at least two geographic populations in the Hawaiian Islands: a Main Hawaiian Islands ( MHI ) population and a Northwestern Hawaiian Islands/Pelagic population ( F ST and Φ ST p .001), as well as an eastern MHI community and a western MHI community ( F ST p = .009). We find genetically driven social structure, or high relatedness among social units and clusters ( p .001), and a positive relationship between relatedness and association between individuals ( p .0001). Further, socially organized clusters are genetically distinct, indicating that social structure drives genetic divergence within the population, likely through restricted mate selection ( F ST p = .05). This genetic divergence among social groups can make the species less resilient to anthropogenic or ecological disturbance. Conservation of this species therefore depends on understanding links among social structure, genetic structure and ecological variability within the species.

Boom‐bust dynamics in biological invasions: towards an improved application of the concept - David L. Strayer; Carla M. D'Antonio; Franz Essl; Mike S. Fowler; Juergen Geist; Sabine Hilt; Ivan Jarić; Klaus Jöhnk; Clive G. Jones; Xavier Lambin; Alexander W. Latzka; Jan Pergl; et al. (Ecology Letters, 2017)
Boom‐bust dynamics – the rise of a population to outbreak levels, followed by a dramatic decline – have been associated with biological invasions and offered as a reason not to manage troublesome invaders. However, boom‐bust dynamics rarely have been critically defined, analyzed, or interpreted. Here, we define boom‐bust dynamics and provide specific suggestions for improving the application of the boom‐bust concept. Boom‐bust dynamics can arise from many causes, some closely associated with invasions, but others occurring across a wide range of ecological settings, especially when environmental conditions are changing rapidly. As a result, it is difficult to infer cause or predict future trajectories merely by observing the dynamic. We use tests with simulated data to show that a common metric for detecting and describing boom‐bust dynamics, decline from an observed peak to a subsequent trough, tends to severely overestimate the frequency and severity of busts, and should be used cautiously if at all. We review and test other metrics that are better suited to describe boom‐bust dynamics. Understanding the frequency and importance of boom‐bust dynamics requires empirical studies of large, representative, long‐term data sets that use clear definitions of boom‐bust, appropriate analytical methods, and careful interpretations.

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Foraging strategies of a generalist marine predator inhabiting a dynamic environment - E. A. McHuron; P. W. Robinson; S. E. Simmons; C. E. Kuhn; M. Fowler; D. P. Costa (Oecologia, 2016)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Navigating the complexity of ecological stability - Ian Donohue; Helmut Hillebrand; José M. Montoya; Owen L. Petchey; Stuart L. Pimm; Mike S. Fowler; Kevin Healy; Andrew L. Jackson; Miguel Lurgi; Deirdre McClean; Nessa E. O'Connor; Eoin J. O'Gorman; et al. (Ecology Letters, 2016)
Human actions challenge nature in many ways. Ecological responses are ineluctably complex, demanding measures that describe them succinctly. Collectively, these measures encapsulate the overall ‘stability’ of the system. Many international bodies, including the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, broadly aspire to maintain or enhance ecological stability. Such bodies frequently use terms pertaining to stability that lack clear definition. Consequently, we cannot measure them and so they disconnect from a large body of theoretical and empirical understanding. We assess the scientific and policy literature and show that this disconnect is one consequence of an inconsistent and one‐dimensional approach that ecologists have taken to both disturbances and stability. This has led to confused communication of the nature of stability and the level of our insight into it. Disturbances and stability are multidimensional. Our understanding of them is not. We have a remarkably poor understanding of the impacts on stability of the characteristics that define many, perhaps all, of the most important elements of global change. We provide recommendations for theoreticians, empiricists and policymakers on how to better integrate the multidimensional nature of ecological stability into their research, policies and actions.

Land colonisation by fish is associated with predictable changes in life history - Edward R. M. Platt; Ashley M. Fowler; Terry J. Ord (Oecologia, 2016)

Tropical cyclone activity in nested regional and global grid-refined simulations - Atsushi Hashimoto; James M. Done; Laura D. Fowler; Cindy L. Bruyère (Climate Dynamics, 2016)

Fitness benefits of serotiny in fire- and drought-prone environments - Casey Lee Causley; William M. Fowler; Byron B. Lamont; Tianhua He (Plant Ecology, 2016)

Temperate predators and seasonal water temperatures impact feeding of a range expanding tropical fish - Hayden J. Beck; David A. Feary; Ashley M. Fowler; Elizabeth M. P. Madin; David J. Booth (Marine Biology, 2016)

Geographically Isolated Wetlands: Rethinking a Misnomer - David M. Mushet; Aram J. K. Calhoun; Laurie C. Alexander; Matthew J. Cohen; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Susan C. Walls (Wetlands, 2015)

Effects of sleep hygiene and artificial bright light interventions on recovery from simulated international air travel - Peter M. Fowler; Rob Duffield; Ian Morrow; Greg Roach; Joanna Vaile (European Journal of Applied Physiology, 2015)

Latitudinal shifts in coral reef fishes: why some species do and others do not shift - David A Feary; Morgan S Pratchett; Micheal J Emslie; Ashley M Fowler; Will F Figueira; Osmar J Luiz; Yohei Nakamura; David J Booth (Fish and Fisheries, 2014)
Climate change is resulting in rapid poleward shifts in the geographical distribution of many tropical fish species, but it is equally apparent that some fishes are failing to exhibit expected shifts in their geographical distribution. There is still little understanding of the species‐specific traits that may constrain or promote successful establishment of populations in temperate regions. We review the factors likely to affect population establishment, including larval supply, settlement and post‐settlement processes. In addition, we conduct meta‐analyses on existing and new data to examine relationships between species‐specific traits and vagrancy. We show that tropical vagrant species are more likely to originate from high‐latitude populations, while at the demographic level, tropical fish species with large body size, high swimming ability, large size at settlement and pelagic spawning behaviour are more likely to show successful settlement into temperate habitats. We also show that both habitat and food limitation at settlement and within juvenile stages may constrain tropical vagrant communities to those species with medium to low reliance on coral resources.

Local native plant diversity responds to habitat loss and fragmentation over different time spans and spatial scales - Karen M. Alofs; Ana V. González; Norma L. Fowler (Plant Ecology, 2014)

Fish assemblages associated with oil industry structures on the continental shelf of north‐western Australia - N. Pradella; A. M. Fowler; D. J. Booth; P. I. Macreadie (Journal of Fish Biology, 2014)
This study provides the first assessment of fish associations with oil and gas structures located in deep water (85–175 m) on Australia's north‐west continental shelf, using rare oil industry video footage obtained from remotely operated vehicles. A diverse range of taxa were observed associating with the structures, including reef‐dependent species and transient pelagic species. Ten commercially fished species were observed, the most abundant of which was Lutjanus argentimaculatus , with an estimated biomass for the two deepest structures (Goodwyn and Echo) of 109 kg.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Risk factors for Staphylococcus aureus nasal colonization in Danish middle-aged and elderly twins - P. S. Andersen; L. A. Larsen; V. G. Fowler; M. Stegger; R. L. Skov; K. Christensen (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

On the influence of tree size on the climate–growth relationship of New Zealand kauri (Agathis australis): insights from annual, monthly and daily growth patterns - Jan Wunder; Anthony M. Fowler; Edward R. Cook; Maryann Pirie; Shane P. J. McCloskey (Trees, 2013)

Development and characterization of 21 polymorphic microsatellite markers for the barren-ground shrew, Sorex ugyunak (Mammalia: Sorcidae), through next-generation sequencing, and cross-species amplification in the masked shrew, S. cinereus - S. A. Sonsthagen; G. K. Sage; M. Fowler; A. G. Hope; J. A. Cook; S. L. Talbot (Conservation Genetics Resources, 2013)

Potential effects of climate change on biological control systems: case studies from New Zealand - P. J. Gerard; J. R. F. Barringer; J. G. Charles; S. V. Fowler; J. M. Kean; C. B. Phillips; A. B. Tait; G. P. Walker (BioControl, 2013)

Loss of native herbaceous species due to woody plant encroachment facilitates the establishment of an invasive grass - Karen M. Alofs; Norma L. Fowler (Ecology, 2013)
Although negative relationships between diversity (frequently measured as species richness) and invasibility at neighborhood or community scales have often been reported, realistic natural diversity gradients have rarely been studied at this scale. We recreated a naturally occurring gradient in species richness to test the effects of species richness on community invasibility. In central Texas savannas, as the proportion of woody plants increases (a process known as woody plant encroachment), herbaceous habitat is both lost and fragmented, and native herbaceous species richness declines. We examined the effects of these species losses on invasibility in situ by removing species that occur less frequently in herbaceous patches as woody plant encroachment advances. This realistic species removal was accompanied by a parallel and equivalent removal of biomass with no changes in species richness. Over two springs, the nonnative bunchgrass Bothriochloa ischaemum germinated significantly more often in the biomass‐removal treatment than in unmanipulated control plots, suggesting an effect of native plant density independent of diversity. Additionally, significantly more germination occurred in the species‐removal treatment than in the biomass‐removal treatment. Changes in species richness had a stronger effect on B. ischaemum germination than changes in plant density, demonstrating that niche‐related processes contributed more to biotic resistance in this system than did species‐neutral competitive interactions. Similar treatment effects were found on transplant growth. Thus we show that woody plant encroachment indirectly facilitates the establishment of an invasive grass by reducing native diversity. Although we found a negative relationship between species richness and invasibility at the scale of plots with similar composition and environmental conditions, we found a positive relationship between species richness and invasibility at larger scales. This apparent paradox is consistent with reports from other systems and may be the result of variation in environmental factors at larger scales similarly influencing both invasibility and richness. The habitat loss and fragmentation associated with woody plant encroachment are two of many processes that commonly threaten biodiversity, including climate change. Many of these processes are similarly likely to increase invasibility via their negative effects on native diversity.

Mobile receivers: releasing the mooring to ‘see’ where fish go - Sean A. Hayes; Nicole M. Teutschel; Cyril J. Michel; Cory Champagne; Patrick W. Robinson; Melinda Fowler; Tina Yack; David K. Mellinger; Samantha Simmons; Daniel P. Costa; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

How well do sunken vessels approximate fish assemblages on coral reefs? Conservation implications of vessel-reef deployments - A. M. Fowler; D. J. Booth (Marine Biology, 2012)

The spawning dynamics of snapper ( Chrysophrys auratus ) in northern Spencer Gulf, South Australia - Richard J Saunders; Anthony J Fowler; Bronwyn M Gillanders (New Zealand Journal of Marine and Freshwater Research, 2012)
This study investigated the inter‐ and intra‐annual variation in the spawning dynamics of snapper ( Chrysophrys auratus ). Reproductive samples from northern Spencer Gulf, South Australia were collected over three seasons (2005/06, 2006/07 and 2007/08) and were analysed macro and microscopically. Spawning activity was determined by calculating estimates of spawning fraction and batch fecundities. The onset of spawning occurred in November but varied between years and corresponded with times when water temperature was between 18 °C and 20 °C. The length of the spawning season also differed between years. In each year the peak spawning activity occurred during December when fish spawned almost daily. Spawning frequency and relative batch size did not differ between the first two spawning seasons but, in the third season, batch size was considerably greater and spawning fractionally lower. These results are contrasted with a known recruitment of 0+ over the three years of the study.

Evidence of sustained populations of a small reef fish on artificial structures. Does depth affect production on artificial reefs? - A. M. Fowler; D. J. Booth (Journal of Fish Biology, 2012)
The length frequencies and age structures of resident Pseudanthias rubrizonatus ( n = 407), a small protogynous serranid, were measured at four isolated artificial structures on the continental shelf of north‐western Australia between June and August 2008, to determine whether these structures supported full (complete size and age‐structured) populations of this species. The artificial structures were located in depths between 82 and 135 m, and growth rates of juveniles and adults, and body condition of adults, were compared among structures to determine the effect of depth on potential production. All life‐history stages, including recently settled juveniles, females and terminal males, of P . rubrizonatus were caught, ranging in standard length ( L s ) from 16·9 to 96·5 mm. Presumed ages estimated from whole and sectioned otoliths ranged between 22 days and 5 years, and parameter ± s.e. estimates of the von Bertalanffy growth model were L ∞ = 152 ± 34 mm, k = 0·15(±0·05) and t 0 = −1·15(±0·15). Estimated annual growth rates were similar between shallow and deep artificial structures; however, otolith lengths and recent growth of juveniles differed among individual structures, irrespective of depth. The artificial structures therefore sustained full populations of P . rubrizonatus , from recently settled juveniles through to adults; however, confirmation of the maximum age attainable for the species is required from natural populations. Depth placement of artificial reefs may not affect the production of fish species with naturally wide depth ranges.

Methanogenic toluene metabolism: community structure and intermediates - S. Jane Fowler; Xiaoli Dong; Christoph W. Sensen; Joseph M. Suflita; Lisa M. Gieg (Environmental Microbiology, 2012)
Summary Toluene is a model compound used to study the anaerobic biotransformation of aromatic hydrocarbons. Reports indicate that toluene is transformed via fumarate addition to form benzylsuccinate or by unknown mechanisms to form hydroxylated intermediates under methanogenic conditions. We investigated the mechanism(s) of syntrophic toluene metabolism by a newly described methanogenic enrichment from a gas condensate‐contaminated aquifer. Pyrosequencing of 16S rDNA revealed that the culture was comprised mainly of Clostridiales . The predominant methanogens affiliated with the Methanomicrobiales . Methane production from toluene ranged from 72% to 79% of that stoichiometrically predicted. Isotope studies using 13 C 7 toluene showed that benzylsuccinate and benzoate transiently accumulated revealing that members of this consortium can catalyse fumarate addition and subsequent reactions. Detection of a BssA gene fragment in this culture further supported fumarate addition as a mechanism of toluene activation. Transient formation of cresols, benzylalcohol, hydroquinone and methylhydroquinone suggested alternative mechanism(s) for toluene metabolism. However, incubations of the consortium with 18 O‐H 2 O showed that the hydroxyl group in these metabolites did not originate from water and abiotic control experiments revealed abiotic formation of hydroxylated species due to reactions of toluene with sulfide and oxygen. Our results suggest that toluene is activated by fumarate addition, presumably by the dominant Clostridiales .

An Evaluation of Boundary-Layer Depth, Inversion and Entrainment Parameters by Large-Eddy Simulation - Ian M. Brooks; Alison M. Fowler (Boundary-Layer Meteorology, 2012)

Modelling the acquisition times of CORONA satellite photographs: accuracy and application - M. J. F. Fowler (International Journal of Remote Sensing, 2011)

Stock discrimination of Southern Garfish (Hyporhamphus melanochir) by stable isotope ratio analysis of otolith aragonite - Mike A. Steer; Galen P. Halverson; Anthony J. Fowler; Bronwyn M. Gillanders (Environmental Biology of Fishes, 2010)

Scavenging and retention of bismuth by marine plankton and biogenic particles - Scott W. Fowler; Jean-Louis Teyssie; Thomas M. Church (Limnology and Oceanography, 2010)
We did radiotracer experiments using 207 Bi to quantify the bioavailability, accumulation, and retention of bismuth in marine plankton and biogenic detritus. The accumulation of 207 Bi by two species of phytoplankton ( Dunaliella tertiolecta and Emiliana huxleyi ) was very rapid, approaching steady state after ~1 d. Emiliana cells without coccoliths reached a volume concentration factor (VCF) roughly twice that attained by cells with coccoliths. VCFs were 5 × 10 5 for Dunaliella and (4–9) × 10 6 for Emiliana after exposure for approximately 5 d. The radioactivity associated with Dunaliella was released with a biological half‐time of 3–5 d. Copepods ( Anomalocera patersoni and Acartia species) grazing radiolabeled Dunaliella assimilated ~4% of the ingested 207 Bi. Unassimilated radioactivity, voided in fecal pellets, was lost from pellets relatively slowly (half‐times of 26 d for Anomalocera and 58 d for Acartia ). These release rates were similar to copepod fecal pellets that had scavenged 207 Bi directly from water. Scavenging of bismuth from water by fecal pellets was considerable and extremely rapid, and uptake rates were similar to those of various size fractions of marine snow collected in a sediment trap. Release of scavenged 207 Bi from the fresh fecal pellets was relatively slow, and very little release of radionuclide from the different size fractions of marine snow was observed. The biogeochemical behavior of bismuth in the marine environment closely resembles that of other particle‐reactive uranium‐thorium (U–Th) series and transuranic elements.

Development of a low-cost system for measuring conditional time-averaged gradients of SO2 and NH3 - D. Famulari; D. Fowler; E. Nemitz; K. J. Hargreaves; R. L. Storeton-West; G. Rutherford; Y. S. Tang; M. A. Sutton; K. J. Weston (Environmental Monitoring and Assessment, 2010)

Clinical characteristics and outcomes of diabetic patients with Staphylococcus aureus bacteremia and endocarditis - Z. A. Kanafani; W. M. Kourany; V. G. Fowler; D. P. Levine; G. A. Vigliani; M. Campion; D. E. Katz; G. R. Corey; H. W. Boucher (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Identification of endangered Hawaiian ducks (Anas wyvilliana), introduced North American mallards (A. platyrhynchos) and their hybrids using multilocus genotypes - Ada C. Fowler; John M. Eadie; Andrew Engilis (Conservation Genetics, 2009)

Are prediction models for Lynch syndrome valid for probands with endometrial cancer? - Floor J. Backes; Heather Hampel; Katherine A. Backes; Luis Vaccarello; George Lewandowski; Jeffrey A. Bell; Gary C. Reid; Larry J. Copeland; Jeffrey M. Fowler; David E. Cohn (Familial Cancer, 2009)

Age‐related movement patterns and population structuring in southern garfish, Hyporhamphus melanochir , inferred from otolith chemistry - M. A. STEER; A. J. FOWLER; B. M. GILLANDERS (Fisheries Management and Ecology, 2009)
The southern garfish, Hyporhamphus melanochir (Val.), is an important inshore fishery species in South Australia. Over the past few years there have been concerns with this fishery, which is now considered to be over‐exploited. Currently, the fishery is assumed to consist of two separate stocks, but there is no understanding of movement patterns both within and between these two stocks to justify this assumption. Otolith chemistry was used to infer age‐related patterns of movement, delineate potential sub‐populations and determine the extent of mixing within South Australian coastal waters. Results indicated that the population structuring of garfish is more complex than previously assumed and it seems that stocks can be discriminated at a much finer spatial scale. Garfish collected from sites separated by 7 Li, 24 Mg, 55 Mn, 88 Sr and 138 Ba) in their otoliths, especially during their second year of growth, indicating that they had inhabited different water bodies. From a broader perspective, South Australian garfish can be partitioned into six regional components with various levels of inter‐mixing. From these results, it was suggested that assessment and management of the fishery may have to be restructured to align with the smaller spatial units.

Analysis of severely affected patients with dihydropyrimidine dehydrogenase deficiency reveals large intragenic rearrangements of DPYD and a de novo interstitial deletion del(1)(p13.3p21.3) - André B. P. van Kuilenburg; Judith Meijer; Adri N. P. M. Mul; Raoul C. M. Hennekam; Jan M. N. Hoovers; Christine E. M. de Die-Smulders; Peter Weber; Andrea Capone Mori; Jörgen Bierau; Brian Fowler; Klaus Macke; Jörn Oliver Sass; et al. (Human Genetics, 2009)

Multi‐model ensemble estimates of climate change impacts on UK seasonal precipitation extremes - H. J. Fowler; M. Ekström (International Journal of Climatology, 2009)
Thirteen regional climate model (RCM) integrations from the Prediction of Regional Scenarios and Uncertainties for Defining European Climate change risks and Effects (PRUDENCE) ensemble are used together with extreme value analysis to assess changes to seasonal precipitation extremes in nine UK rainfall regions by 2070–2100 under the SRES A2 emissions scenario. Model weights are based on similarities between observed and modelled UK extreme precipitation calculated for a combination of (1) spatial characteristics: the semi‐variogram parameters sill and range, and (2) the discrepancy in the regional median seasonal maxima. These weights are used to combine individual RCM bootstrap samples to provide multi‐model ensemble estimates of percent change in the return value magnitudes of regional extremes. The contribution of global climate model (GCM) and RCM combinations to model structural uncertainty is also investigated. The multi‐model ensembles project increases across the UK in winter, spring and autumn extreme precipitation; although there is uncertainty in the absolute magnitude of increases, these range from 5 to 30% depending upon region and season. In summer, model predictions span the zero change line, although there is low confidence due to poor model performance. RCM performance is shown to be highly variable; extremes are well simulated in winter and very poorly simulated in summer. The ensemble distributions are wider (projections are more uncertain) for shorter duration extremes (e.g. 1 day) and higher return periods (e.g. 25 year). There are rather limited differences in the weighted and unweighted multi‐model ensembles, perhaps a consequence of the lack of model independence between ensemble members. The largest contribution to uncertainty in the multi‐model ensembles comes from the lateral boundary conditions used by RCMs included in the ensemble. Therefore, the uncertainty bounds shown here are conservative despite the relatively large number of RCMs contributing to the multi‐model ensemble distribution. Copyright © 2009 Royal Meteorological Society

A history of ENSO events since A.D. 1525: implications for future climate change - Joëlle L. Gergis; Anthony M. Fowler (Climatic Change, 2009)

Transgenic mice expressing the Peripherin-EGFP genomic reporter display intrinsic peripheral nervous system fluorescence - Samuel McLenachan; Yona Goldshmit; Kerry J. Fowler; Lucille Voullaire; Timothy P. Holloway; Ann M. Turnley; Panos A. Ioannou; Joseph P. Sarsero (Transgenic Research, 2008)

Candida infective endocarditis - J. W. Baddley; D. K. Benjamin; M. Patel; J. Miró; E. Athan; B. Barsic; E. Bouza; L. Clara; T. Elliott; Z. Kanafani; J. Klein; S. Lerakis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Apparent competition can compromise the safety of highly specific biocontrol agents - Luisa G. Carvalheiro; Yvonne M. Buckley; Rita Ventim; Simon V. Fowler; Jane Memmott (Ecology Letters, 2008)
Despite current concern about the safety of biological control of weeds, assessing the indirect impacts of introduced agents is not common practice. Using 17 replicate food webs, we demonstrate that the use of a highly host‐plant specific weed biocontrol agent, recently introduced into Australia, is associated with declines of local insect communities. The agent shares natural enemies (predators and parasitoids) with seed herbivore species from native plants, so apparent competition is the most likely cause for these losses. Both species richness and abundance in insect communities (seed herbivores and their parasitoids) were negatively correlated with the abundance of the biocontrol agent. Local losses of up to 11 species (dipteran seed herbivores and parasitoids) took place as the biocontrol agent abundance increased. Ineffective biocontrol agents that remain highly abundant in the community are most likely to have persistent, indirect negative effects. Our findings suggest that more investment is required in pre‐release studies on the effectiveness of biocontrol agents, as well as in post‐release studies assessing indirect impacts, to avoid or minimize the release of potentially damaging species.

Could krill schools significantly bias 234Th‐based carbon flux models? - Alessia M. Rodriguez y Baena; Scott W. Fowler; Michel Warnau (Limnology and Oceanography, 2008)
To test the recent hypothesis that krill schools and their molting can hinder the accuracy of 234T h‐based particle flux models under specific conditions, radiotracer experiments were conducted with northern krill, Meganyctiphanes norvegica , to examine how 23 4Th uptake and release kinetics may affect residual 234 Th concentrations in seawater. Krill rapidly took up 234 Th from seawater, reaching a steady‐state concentration factor of ~180 in less than 1 week, and strongly retained the accumulated radionuclide until molting occurred. The nine molting events observed during the 18‐d experimental period indicated that ~50% of krill whole‐body 234 Th activity was associated with the cast exoskeleton, and that a corresponding amount was rapidly adsorbed postecdysis on the newly formed cuticle. In regions characterized by the occurrence of high planktonic crustacean biomass, failure to link the presence of organisms with their effects on 234 Th dynamics in the water column may induce significant biases (in some circumstances, up to one order of magnitude) in 234 Th‐derived particulate organic carbon flux estimations or sediment trap efficiency calculations based on this method. However, because of the patchy distribution of dense aggregations of krill, the overall likelihood of such dramatic modeling artifacts is estimated to be relatively low (≤5% per sampling time).

ENSO history recorded in Agathis australis (kauri) tree rings. Part B: 423 years of ENSO robustness - A. M. Fowler (International Journal of Climatology, 2008)
Part A of this study identified the potential of kauri tree rings for reconstructing the history of past ENSO activity. Plausible indices of multidecadal to centennial‐scale ENSO activity (phase dominance and robustness) that could be derived from kauri regional master chronologies are hypothesized here, and they are tested against the instrumental SOI record, using partitioning and graphical analyses. The subset of the indices passing this first screening are then tested for sensitivity to the complex evolving sample depth and site‐composition mix that characterizes regional tree‐ring chronologies. Corrections for evolving sample depth are developed where possible. The two indices of ENSO activity remaining after these two screening phases (evolving chronology time‐series variance and decadal‐scale spectral signature) are used to infer 423 years of ENSO robustness and the results are compared to two multiproxy ENSO reconstructions. Results suggest that ENSO robustness (1) peaked in the 20th century, (2) is characterized by persistent 55–80 year cyclicity, (3) was low in the mid‐20th century only relative to robust ENSO activity at the beginning and end of that century, (4) reached a pre‐20th century peak in the mid‐18th century, and (5) was weakest near the beginning of the 19th century. Copyright © 2007 Royal Meteorological Society

ENSO history recorded in Agathis australis (kauri) tree rings. Part A: kauri's potential as an ENSO proxy - A. M. Fowler; G. Boswijk; J. Gergis; A. Lorrey (International Journal of Climatology, 2008)
Although many of the main characteristics of the El Niño‐Southern Oscillation (ENSO) phenomenon have been established, uncertainties remain concerning its multidecadal‐ to millennial‐scale evolution. Because of the shortness of the instrumental record, we need to resort to proxy‐based reconstructions to investigate ENSO's history prior to the mid 19th century, but the available proxy data is limited in both time and space. Here we investigate the potential for ENSO reconstruction from the tree rings of Agathis australis (kauri). Kauri is a long‐lived endemic New Zealand conifer and grows in an ENSO teleconnection region not previously represented in ENSO multi‐proxy studies. A high quality 423 year kauri regional master chronology (AD 1580–2002) is constructed. Statistical analysis of the period AD 1876–2002 confirms previous findings that kauri tree rings carry a strong regional‐scale climate signal and that ENSO is a significant contributor (predominantly via the western pole of the Southern Oscillation). Kauri carries a signal of both ENSO phases, but with a slight El Niño bias. Growth sensitivity is primarily registered through a five‐season window, extending from March (prior to growth initiation in September) through to the following May, with strongest relationships across the middle three seasons (June–February). Relationships appear to be stationary. We conclude that kauri has sufficient ENSO event capture skill to make it a useful addition to future multi‐proxy ENSO reconstruction efforts. It may also have potential for stand‐alone reconstruction of multidecadal‐ to millennial‐scale evolution of ENSO activity, especially ENSO robustness. Copyright © 2007 Royal Meteorological Society

Reconstructing past biological invasions: niche shifts in response to invasive predators and competitors - Meg M. Eastwood; Megan J. Donahue; Amy E. Fowler (Biological Invasions, 2007)

National Threatened Species Listing Based on IUCN Criteria and Regional Guidelines: Current Status and Future Perspectives - REBECCA M. MILLER; JON PAUL RODRÍGUEZ; THERESA ANISKOWICZ‐FOWLER; CHANNA BAMBARADENIYA; RUBEN BOLES; MARK A. EATON; ULF GÄRDENFORS; VERENA KELLER; SANJAY MOLUR; SALLY WALKER; CAROLINE POLLOCK (Conservation Biology, 2007)
As countries worldwide become increasingly interested in conserving biodiversity, the profile of national threatened species lists expands and these lists become more influential in determining conservation priorities. The World Conservation Union (IUCN) Categories and Criteria for evaluating extinction risk, originally intended for use at the global level, are increasingly being used at the national level. To facilitate this process, the IUCN recently published guidelines for the application of the criteria at subglobal levels. We evaluated the application of these guidelines, focusing on the opinions and experience of the global community of national assessors. To assess the extent to which IUCN criteria have been used in official national listing efforts, we sent a survey to 180 Convention on Biological Diversity national focal points designated by governments. Of the respondents, 77% had developed national threatened species lists. Of these, 78% applied a version of the IUCN criteria, and 88% plan to produce future threatened species lists. The majority of this last group (83%) will use IUCN criteria. Of the countries that have or will develop a threatened species list, 82% incorporated their list or the IUCN criteria into national conservation strategies. We further explored the issues highlighted by the survey results by integrating the experience of assessors that have produced national lists. Most of the problems national assessors faced when applying the IUCN criteria arose when the criteria were applied at the regional level without the IUCN Regional Guidelines and when assessors were confused about the purpose of the IUCN criteria and lacked training in their proper use. To improve their clarity and increase their repeatability, we recommend that the IUCN increase communication and information exchange among countries and between regional and global assessors, potentially through an interactive Web site, to facilitate the development of national red lists and to improve their conservation value within and between countries.

Particulate organic carbon : natural radionuclide ratios in zooplankton and their freshly produced fecal pellets from the NW Mediterranean (MedFlux 2005) - Alessia M. Rodriguez y Baena; Scott W. Fowler; Juan Carlos Miquel (Limnology and Oceanography, 2007)
To discern controls on particulate organic carbon (POC) : natural radionuclide (RN) ratio variability in order to enhance the accuracy of water column radionuclide‐based carbon flux estimates, 234 Th, 210 Po, and POC were analyzed in seven size classes of mixed micro‐ and mesoplankton (1‐1,500‐µm size range), in larger zooplankton from different taxa (salps, euphausiids, copepods, pteropods), and in freshly produced feces from zooplankton collected during spring in the NW Mediterranean. POC:RN ratios in zooplankton ranged between 120 and 11,600 and between 89 and 9,200 µmol dpm −1 for 234 Th and 210 Po, respectively. In fecal pellets, POC:RN ratios were one to three orders of magnitude lower for 234 Th and 3‐fold to 30‐fold lower for 210 Po; the only exception was euthecosome pteropods, which had a higher POC: 210 Po ratio in their pellets than in their whole bodies. Significant increases in POC:RN ratios with organism size were best described by a power relationship for POC: 234 Th (p 210 Po (with a constant POC: 210 Po ratio above 70 µm; p 234 Th and food chain bioaccumulation for 210 Po. This inference is further supported by the observation that, for the >33‐µm size classes, 210 Po specific activity correlates negatively with the surface : volume ratio, while 234 Th correlates positively with it (p 234 Th flux; however, it could considerably bias similar measurements of 210 Po flux as well as those of POC:RN ratios.

Estimated Sand and Gravel Resources of the South Merrimack, Hillsborough County, New Hampshire, 7.5-Minute Quadrangle - David M. Sutphin; Lawrence J. Drew; Brian K. Fowler (Natural Resources Research, 2007)

Cellular distribution of calcium current is unaltered during compensated hypertrophy in the spontaneously hypertensive rat - Mark R. Fowler; Clive H. Orchard; Simon M. Harrison (Pflügers Archiv - European Journal of Physiology, 2006)

Millennia‐long tree‐ring records from Tasmania and New Zealand: a basis for modelling climate variability and forcing, past, present and future - Edward R. Cook; Brendan M. Buckley; Jonathan G. Palmer; Pavla Fenwick; Michael J. Peterson; Gretel Boswijk; Anthony Fowler (Journal of Quaternary Science, 2006)
Progress in the development of millennia‐long tree‐ring chronologies from Australia and New Zealand is reviewed from the perspective of modelling long‐term climate variability there. Three tree species have proved successful in this regard: Huon pine ( Lagarostrobos franklinii ) from Tasmania, silver pine ( L. colensoi ) from the South Island of New Zealand, and kauri ( Agathis australis ) from the North Island of New Zealand. Each of these species is very long‐lived and produces abundant quantities of well‐preserved wood for extending their tree‐ring chronologies back several millennia into the past. The growth patterns on these chronologies strongly correlate with both local and regional warm‐season temperature changes over significant areas of the Southern Hemisphere (especially Huon and silver pine) and to ENSO variability emanating from the equatorial Pacific region (especially kauri). In addition, there is evidence for significant, band‐limited, multi‐decadal and centennial timescale variability in the warm‐season temperature reconstruction based on Huon pine tree rings that may be related to slowly varying changes in ocean circulation dynamics in the southern Indian Ocean. This suggests the possibility of long‐term climate predictability there. Copyright © 2006 John Wiley & Sons, Ltd.

Prosthetic valve endocarditis due to coagulase-negative staphylococci: findings from the International Collaboration on Endocarditis Merged Database - T. Lalani; Z. A. Kanafani; V. H. Chu; L. Moore; G. R. Corey; P. Pappas; C. W. Woods; C. H. Cabell; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; C. Chirouze; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Enterococcal prosthetic valve infective endocarditis: report of 45 episodes from the International Collaboration on Endocarditis-merged database - D. J. Anderson; L. Olaison; J. R. McDonald; J. M. Miro; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; E. Abrutyn; G. Habib; S. Eykyn; P. A. Pappas; V. G. Fowler; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Classification of synchronous oceanic and atmospheric El Niño-Southern Oscillation (ENSO) events for palaeoclimate reconstruction - Joëlle L. Gergis; Anthony M. Fowler (International Journal of Climatology, 2005)

Variation at local scales need not impede tests for broader scale patterns - Meegan J. Fowler-Walker; Sean D. Connell; Bronwyn M. Gillanders (Marine Biology, 2005)

Use of Radiotracer Techniques to Study Subcellular Distribution of Metals and Radionuclides in Bivalves from the Noumea Lagoon, New Calendonia - M. Metian; L. Hédouin; C. Barbot; J.-L. Teyssié; S. W. Fowler; F. Goudard; P. Bustamante; J.-P. Durand; J. Piéri; M. Warnau (Bulletin of Environmental Contamination and Toxicology, 2005)

Human BAC-mediated rescue of the Friedreich ataxia knockout mutation in transgenic mice - Joseph P. Sarsero; Lingli Li; Timothy P. Holloway; Lucille Voullaire; Sophie Gazeas; Kerry J. Fowler; Denise M. Kirby; David R. Thorburn; Adam Galle; Surindar Cheema; Michel Koenig; Robert Williamson; et al. (Mammalian Genome, 2004)

Molecular and morphological analyses of the cuttlefish Sepia apama indicate a complex population structure - K. S. Kassahn; S. C. Donnellan; A. J. Fowler; K. C. Hall; M. Adams; P. W. Shaw (Marine Biology, 2003)

Hypervariability of the membrane-associated mucin and cancer marker MUC1 - Joanna C. Fowler; Ana S. Teixeira; Lynne E. Vinall; Dallas M. Swallow (Human Genetics, 2003)

Effects of water-soluble cigarette smoke extracts upon the release of ?-hexosaminidase from RBL-2H3 basophilic leukaemia cells in response to substance P, compound 48/80, concanavalin A and antigen stimulation - C. J. Fowler; M. Sandberg; G. Tiger (Inflammation Research, 2003)

Coprecipitation of nonoxynol-9 with polyvinylpyrrolidone to decrease vaginal irritation potential while maintaining spermicidal potency - Philip T. Fowler; Gustavo F. Doncel; Paul M. Bummer; George A. Digenis (AAPS PharmSciTech, 2003)

AM404 and VDM 11 non-specifically inhibit C6 glioma cell proliferation at concentrations used to block the cellular accumulation of the endocannabinoid anandamide - Kent-Olov Jonsson; Anna Andersson; Stig O. P. Jacobsson; Séverine Vandevoorde; Didier M. Lambert; Christopher J. Fowler (Archives of Toxicology, 2003)

5-Lipoxygenase polymorphism and in-vivo response to leukotriene receptor antagonists - Stephen J. Fowler; Ian P. Hall; Andrew M. Wilson; Amanda P. Wheatley; Brian J. Lipworth (European Journal of Clinical Pharmacology, 2002)

Annual methane emission from Finnish mires estimated from eddy covariance campaign measurements - K. J. Hargreaves; D. Fowler; C. E. R. Pitcairn; M. Aurela (Theoretical and Applied Climatology, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Behavioral tolerance to the force differentiation effects of diazepam and midazolam in rats - S. E. Bowen; S. C. Fowler; J. A. Stanford; M. J. Kallman (Psychopharmacology, 2000)

CHARACTERIZATION OF JOK-1, A HUMAN GASTRIC EPITHELIAL CELL LINE - N. OKAYAMA; M. R. FOWLER; S. R. JENNINGS; P. PATEL; R. SPECIAN; B. ALEXANDER; T. H. JACKSON; T. OSHIMA; K. SHANNON; J. S. ALEXANDER (In Vitro Cellular & Developmental Biology - Animal, 2000)

The effect of termite biomass and anthropogenic disturbance on the CH 4 budgets of tropical forests in Cameroon and Borneo - J. A. Macdonald; D. Jeeva; P. Eggleton; R. Davies; D. E. Bignell; D. Fowler; J. Lawton; M. Maryati (Global Change Biology, 1999)
Summary The exchange of CH 4 between tropical forests and the atmosphere was determined by simultaneously measuring the net CH 4 flux at the soil surface and assessing the flux contribution from soil‐feeding termite biomass, both within the soil profile and in mounds. In Cameroon the flux of CH 4 ranged from a net emission of 40.7 ng m –2 s –1 to a net CH 4 oxidation of –53.0 ng m –2 s –1 . Soil‐inhabiting termite biomass was significantly correlated with CH 4 flux. Termite mounds emitted up to 2000 ng s –1 mound –1 . Termite‐derived CH 4 emission reduced the soil sink strength by up to 28%. Disturbance also had a strong effect on the soil sink strength, with the average rate of CH 4 oxidation, at – 17.5 ng m –2 s –1 , being significantly smaller (≈ 36%) at the secondary forest site than the –27.2 ng m –2 s –1 , observed at the primary forest site. CH 4 budgets calculated for each site indicated that both forests were net sinks for CH 4 at – 6.1 kg ha –1 y –1 in the near‐primary forest and – 3.1 kg ha –1 y –1 in the secondary forest. In Borneo, three forest sites representing a disturbance gradient were examined. CH 4 oxidation rates ranged from 0 to – 32.1 ng m –2 s –1 and a significant correlation between the net flux and termite biomass was observed only in an undisturbed primary forest, although the biomass was insufficient to cause net emission of CH 4 . Rates of CH 4 oxidation were not significantly different across the disturbance gradient but were, however, larger in the primary forest (averaging – 15.4 ng m –2 s –1 ) than in an old‐growth secondary forest (–13.9 ng m –2 s –1 ) and a young secondary re‐growth (– 10.8 ng m –2 s –1 ). CH 4 flux from termite mounds ranged from net oxidation in an abandoned mound to a maximum emission of 468 ng s –1 mound –1 . CH 4 budgets calculated for each site indicated that CH 4 flux from termite mounds had an insignificant effect on the budget of CH 4 at the regional scale at all three forest sites. Annual oxidation rates were – 4.8, – 4.2 and – 3.4 kg ha –1 y –1 in the primary, secondary and young secondary forests, respectively.

Deposition Monitoring in Europe - J. W. Erisman; M. G. Mennen; D. Fowler; C. R. Flechard; G. Spindler; A. Grüner; J. H. Duyzer; W. Ruigrok; G. P. Wyers (Environmental Monitoring and Assessment, 1998)

Quantifying Fine-Scale Variability in Pollutant Deposition in Complex Terrain using 210Pb Inventories in Soil - D. Fowler; R.I. Smith; I.D. Leith; A. Crossley; R.W. Mourne; D.W. Branford; M. Moghaddam (Water, Air, & Soil Pollution, 1998)

Opioid modulation of attention-related responses: peripheral-to-central progression and development of mu influence as learning occurs - L. L. Hernández; Karen L. Watson; Bradley M. Fowler; Kirk D. Bair; Amrita K. Singha (Psychopharmacology, 1997)

Integration of trinucleotide microsatellites into a linkage map of Citrus - J. M. H. Kijas; M. R. Thomas; J. C. S. Fowler; M. L. Roose (Theoretical and Applied Genetics, 1997)

Nephrotoxicity of 4-amino-3-S-glutathionylphenol and its modulation by metabolism or transport inhibitors - Lynn M. Fowler; John R. Foster; Edward A. Lock (Archives of Toxicology, 1994)

Effect of ascorbic acid, acivicin and probenecid on the nephrotoxicity of 4-aminophenol in the Fischer 344 rat - Lynn M. Fowler; John R. Foster; Edward A. Lock (Archives of Toxicology, 1993)

Oviposition pattern byCotesia ayerzai [Hym.: Braconidae] onAscia monuste [Lep.: Pieridae] under laboratory conditions - N. Gobbi; M. C. A. Cunha; R. Zucchi; H. G. Fowler (BioControl, 1990)

Transformation of rabbit arterial smooth muscle cells with Simian virus 40 - M. Nachtigal; P. Greenspan; L. Terracio; S. D. Fowler (Archives of Virology, 1987)

Genetics of the mammalian phenylalanine hydroxylase system. IV. Evidence of phenylalanine hydroxylase in a cultured human hepatoma cell line - K. H. Choo; R. G. H. Cotton; I. G. Jennings; K. Fowler; D. M. Danks (Biochemical Genetics, 1980)

Sectional notes - Cecil W. Frutchey; W. B. Ward; Marx Koehnke; J. C. Campbell; H. J. Evans; Earl B. Tussing; O. D. Burke; John Noonan; M. R. Harris; Wm. A. Riedl; W. A. Fowler (American Journal of Potato Research, 1947)